Spin-influenced oxygen evolution driven by a honeycomb quantum magnet - Ghulam Hussain; Shuyi Li; Man Zhang; Bing Wang; Xinyan Dai; Shengyu Sun; Xiaoqi Zhou; Vladimir Presnov; Ziquan Wang; Yici Li; Xiawa Wang (Chemical Engineering Journal, 2026)

Sprayable androgen receptor PROTAC degrader for immunomodulation and accelerated skin regeneration - Se Youn Jang; Byeongmin Park; Eunbyeol Ko; Dongwon Shin; Yeongji Jang; Woohyeong Lee; Jae-Hyeon Lee; Ansoo Lee; Jooho Park; Sangmin Lee; Hyun Kyu Song; Yoosoo Yang; et al. (Chemical Engineering Journal, 2026)

Differentiation of block-scale carbon budgets and synergistic carbon reduction pathways under functional guidance and spatial constraints: Evidence from Wuxi, China - Hui Guo; Wei Sun; Sen Wang; Man Li (Sustainable Cities and Society, 2026)

Structure and bioactivity of protolimonoids from the root bark of Dictamnus dasycarpus Turcz. - Hua Yue; Zi-Xuan Li; Zi-Tong Hao; Dan Zeng; Jie Bao; Ling-Zhi Zhang; Xue-Man Lin; Hua Sun; Shu-Fang Li; Su-Juan Wang (Phytochemistry, 2026)

Full mechanical response prediction for staged prestressed composite beams driven by a hybrid GRU-VAE and BiLSTM framework - Zexuan Sun; Tianxia Cui; Man Xu; Bin Zeng; Chun-Lin Wang (Engineering Structures, 2026)

Starch granular hydrogels with enhanced mechanical properties and 3D printing performance: Fabrication and characterization - Ying Wang; Ziyun Zhao; Man Li; Yang Qin; Liu Xiong; Qingjie Sun (Carbohydrate Polymers, 2026)

Allelic variation in cis-regulation of UNE12 underlies differential Verticillium wilt resistance in tetraploid cottons - Meixia Xie; Ziming Li; Jiaxuan Zhao; Minghui Ye; Mengjia Jiao; Zhicheng Wang; Xinxin Zheng; Xinyu Zhang; Jin Zhang; Yan Wang; Man Gu; Lingxia Zhai; et al. (Science Bulletin, 2026)

A state-of-the-art review in legume protein gelation: mechanisms, structure-function relationships, modification strategies, and emerging food applications - Xiangxiao Kong; Wenting Tang; Man Li; Qingjie Sun; Chuanfen Pu (Food Research International, 2026)

Controlling the properties of 3D-printed sodium caseinate emulsion gels by tuning starch-induced network architecture - Kangning Zhang; Fangyuan Tian; Xiaojing Li; Shengju Ge; Yanping Wang; Yang Qin; Man Li; Rongbo Fan; Qingjie Sun; Na Ji (Food Research International, 2026)

Inhibition of digestive enzymes with EGCG-loaded inverse alginate beads: a strategy for modulating starch digestion - Xiya Zhang; Jinling Zou; Shengju Ge; Xiaojing Li; Meng Li; Yang Qin; Man Li; Qingjie Sun; Jian He; Na Ji (Food Chemistry, 2026)

Zein-calcium alginate dual-shell liquid-core beads for tailored starch digestibility: Structural design, functional performance, and mechanistic analysis - Yang Qin; Xiya Zhang; Jinling Zou; Shengju Ge; Xiaojing Li; Man Li; Qingjie Sun; Qingze Han; Huanying Qin; Jian He; Na Ji (Food Chemistry, 2026)

Targeting the phenolic A-ring unifies the toxicology and remediation of environmental estrogens in aquatic environments - Liu-Feng Yu; Yi-Lin Ye; Jie Zhou; Yu-Han Jin; Yu-Han Sun; Li-Xia Yan; Chen-Man Li; Jia-Yi Chang; Wei-Jie Chen; Feng Liu; Yong-Wei Feng; Xiao-Dong Huang; et al. (Environmental Research, 2026)

Combined exposure to hypoxia and 17α-ethinylestradiol alters reproductive traits in marine medaka - Xian Qin; Jiezhang Mo; Huiju Lin; Yi Yang; Emily Sze Wan Wong; Min Pan; Sidney Man Ngai Chan; Rudolf Shiu Sun Wu; William Ka Fai Tse; Keng Po Lai (Aquatic Toxicology, 2026)

A reconstruction method of missing torque data using a simplified neuromusculoskeletal (NMS) model - Zhe Sun; Xiaoyun Bi; Lubin Hong; Jinchuan Zheng; Zhihong Man (Medical & Biological Engineering & Computing, 2026)

Spatial engineering of adjacent pair single-atom catalyst for reaction-pathway decoupling in advanced oxidation - Man Yang; Yongquan Zhu; Jing Mei; Haibo Li; Wengang Liu; Jing Lu; Jie Cui; Shaodong Sun; Yang Song; Xinyang Liu; Yujing Ren (Journal of Hazardous Materials, 2026)

Priority control of potentially toxic elements in urban park soils through integrated source apportionment and health risk assessment - Xiangtian Man; Jian Sun; Xingnian Ren; Mengli Chen; Cheng Yang; Ruxin Yang; Ailian Li; Junfang Cui; Han Zhang (Environmental Geochemistry and Health, 2026)

Grounding transnational railway infrastructuralism along the China-Laos Railway assemblage - Tao Song; Man Sun; Zhouying Song (Journal of Geographical Sciences, 2026)

Cell identity uncertainty and exposure heterogeneity in germ cell-resolved comet assays - Man Sun; Dan Zang; Jun Chen (Archives of Toxicology, 2026)

Super-resolution multimodal spatial transcriptomics reveals an ovoid stem cell niche structuring de novo shoot regeneration - Xiehai Song; Shaoman Zhang; Zhiliang Yue; Yongqi Liu; Shanshan Chen; Yani Niu; Yan Shi; Hengjia Yang; Jiahao Xu; Yuanyuan Miao; Meizhi Xu; Yingxue Zhou; et al. (Molecular Plant, 2026)

Long-term aging of oxychar and biochar: structural, adsorptive, and microbial transformations - Cheng Ji; Shutao Wang; Man Zhang; Hang Sun; Qinggang Meng; Kexin Zhao; Yifan Li; Shiming Su; Bing Han; Wei Liu (Fuel, 2026)

Mechanistic insights into Salmonella growth kinetics under solute-induced water activity stresses via transcriptomics and NMR analysis - Zheneng Sun; Man Tian; Ziqi Zeng; Yuhuan Liu; Shuxiang Liu (Food Research International, 2026)

Burdock leaf polysaccharide as a clean-label bio-preservative for meat: Structural characterization, multifaceted antibacterial mechanisms, and shelf-life extension efficacy - Yong-xin Li; Chan Zhang; Linchong Hui; Xiangfeng Liu; Yuting Sun; Man Liu; Jun Tian (Food Chemistry, 2026)

Simulating ecosystem resilience: Tipping point evasion driven by adaptive plant-pollinator interaction - Le Jiao; Peng Zhang; Man Qi; Heyue Zhang; Alfred Stein; Tao Sun (Journal of Environmental Management, 2026)

Epigenetic impacts of the acaricide flumethrin on honeybees (Apis mellifera) - Xue Wang; Suzhen Qi; Mu Ding; Wei Zhang; Aidi Huang; Changlu Sun; Man Fan; Liming Wu; Miao Wang (Environmental Pollution, 2026)

λ-Carrageenan inhibits African swine fever virus infection potentially through its interaction with the viral envelope protein CD2v - Kun Han; Limeng Sun; Can Jin; Siqi Wan; Caiqin Cao; Yulu Yue; Man Lu; Xiaotong Wang; Yi Zheng; Hailong Liu; Yilin Guo; Dagang Tao; et al. (Carbohydrate Polymers, 2026)

Specificity of polyclonal oligopeptide antisera targeting glycoprotein hormones from the Japanese Eel (Anguilla japonica) - Hyun-Sol Jo; Tae-Ha Kim; Jae Man Lee; Young Chang Sohn; Tae-Won Goo; Sun-Mee Hong (Biotechnology Letters, 2026)

Highly cadmium and chromium tolerant rhizosphere bacteria of Albizia julibrissin Durazz on plant growth promoting - Xinyu Wu; Mengyu Zhang; Chen Du; Mengru Sun; Houpeng Hu; Man Cai (BioMetals, 2026)

Unraveling hydration and physicochemical property modulation in potato starch gels through multiscale structural orientation induced by uniaxial stretching–drying - Liu Xiong; Yuting He; Xianzhi Liu; Man Li; Zhongxiu Wang; Shengtian Zhang; Qingjie Sun (Food Hydrocolloids, 2026)

Cumulative macro-microscopic fatigue damage of hard rock under three-dimensional cyclic impact loading - Yunfeng Wu; Changhong Li; Peng Li; Yu Wang; Dan Ma; Erhui Zhang; Changkun Sun; Prabhat Man Singh Basnet (Bulletin of Engineering Geology and the Environment, 2026)

Application of Magnetic-Seismic Geophysical Prospecting Technology in Identifying the Carboniferous Volcanic Rocks in the Chepaizi, West Margin of Junggar Basin - Guo-hua Jiao; Wei-ping Zhang; Jin-ke Zhou; Fu-gang Sun; Hai-tao Yang; Man Li; Zhu-qiang Li (Applied Geophysics, 2026)

Advances in high-performance alginate hydrogels: properties, performance enhancement strategies, and their applications in the food industry - Jiabo Wang; Yuanpu Liu; Chuanwu Han; Zhihui Liu; Yumeng Yue; Zhiyuan Yu; Meng Ma; Qingjie Sun; Fengwei Xie; Man Li (Trends in Food Science & Technology, 2026)

Biochar and phosphogypsum in agricultural soils: Individual roles, combined potentials, and future prospects - Yiwen WANG; Man QI; Changfu YANG; Ruyu SUN; Hanbing LI; Yawen ZHAO; Li WANG (Pedosphere, 2026)

The F-box protein ZmFBK1 facilitates autophagy-mediated degradation of maize NLR protein Rp1-D21 to suppress the hypersensitive response - Chang-Xiao Tang; Shi-Jun Ma; Qi-Dong Ge; Yang Sun; Tong-Tong Liu; Man Yang; Zi-Xuan Kang; Yu-Chen Dai; Xuan Zhang; Xueman Liu; Yanyong Cao; Guan-Feng Wang (Molecular Plant, 2026)

Asynchronous abrupt changes of lake ecosystems in the Anthropocene - Dinggui Wu; Tian Xia; Qingfeng Zhao; Yibin Sun; Na Song; Man Li; Tianchen He (Global and Planetary Change, 2026)

Natural sugar substitute Rebaudioside M: Efficient and cost-effective biosynthesis via host engineering, cascade biocatalysis, and substrate feeding - Xiang Luo; Yang Wang; Man Zhou; Qiaolan Sun; Xue Wang; Xiaojie Yu; Li Chen; Hua Yang; Cunshan Zhou (Food Chemistry, 2026)

Modulation of highland barley noodles quality by water-soluble polyphenols epigallocatechin gallate and ferulic acid - Mengting Wang; Yulin Wu; Zichu Wang; Yu Jiang; Yanfei Wang; Chuanwu Han; Yang Li; Jichun Tian; Meng Ma; Qingjie Sun; Fengwei Xie; Man Li (Food Chemistry, 2026)

Effects of water table depth and fluctuations on Sphagnum palustre growth and plant community succession in subtropical mountainous Sphagnum peatlands: insights from a microcosm experiment - Ting-Ting Li; Man-Jing Tian; Jie Xu; Lun-Che Wang; Bin-Luo Li; Hui-Hui Sun; Wen-Yi Yang; Zheng-Xiang Wang (Aquatic Sciences, 2026)

Intensified sediment transport by breakdown of discharge-induced two-layer circulation in a contaminated, macro-tidal bay - Jae Hyeok Shin; Sun Min Choi; Kyung Man Kim; Ho Kyung Ha (Marine Pollution Bulletin, 2026)

Curdlan modulates potato starch gelatinization and gelation: Mechanisms of interaction, structural enhancement, and texture improvement in hydrogel foods - Yongxin Liu; Xinyi Li; Liya Chen; Fan Feng; Chang Sun; Yingchao Xu; Xinyu Sun; Man Li; Qingjie Sun; Xingfeng Xu; Fengwei Xie; Yanfei Wang (Food Hydrocolloids, 2026)

Ultrahigh efficiency uranium extraction from seawater using Ni0-modified boron nitride: Mechanistic insights and practical application - Yixin Pan; Mingze Qin; Yingying Zhou; Bo Sun; Man Huang; Xichun Tian; Ruichao Mao; Hongliang Dong (Desalination, 2026)

Analysis of spatiotemporal coupling relationships and driving mechanisms between climatic factors and winter wheat yield in the Yudong Grain Production Core Area - Qingtao Zhao; Guodong Li; Xiaojuan Ren; Man Zhang; Jingyu Wang; Xuejian Sun; Longsheng Wang; Yunfei Gong (Theoretical and Applied Climatology, 2026)

An integrated approach combining computational analyses and experimental validation deciphers the mechanism and active substance basis of Huazhuo Ningfu decoction in treating psoriasis - Zitong Guan; Mengxue Han; Xiaolin Wang; Wenke Ma; Shasha Shi; Hao Jiang; Jiazheng Sun; Ping Cao; Shuai Man (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Reverse temporal spectral signal extraction and deep spectral signal decoupling fusion for detection of SCLB infection process - Guohui Liu; Jinyang Chao; Changle Guo; Lulu An; Yang Liu; Hong Sun; Chunqi Zhang; Mingjia Liu; Zheng Cui; Man Zhang; Minzan Li; Wei Yang (Computers and Electronics in Agriculture, 2026)

Fabrication of sulfonated polypropylene melt-blown cloth-supported L-cysteine-functionalized defective Ce-Uio-66-NH₂ composites with enhanced Cu(Ⅱ) sequestration performance - Yi-Man Sun; Xue-Qi Fan; Song-Yang Yue; Le Tao; Shu-Xia Guan; De-Bin Ji (Journal of Environmental Chemical Engineering, 2026)

Enhanced photocatalytic uranium(VI) removal via oxygen vacancy-assisted Z-scheme SPC-Bi/Bi2WO6 with plasmonic Bi activation - Le Tao; Xue-Qi Fan; Yi-Man Sun; Yue Hu; Wen-Yan Guo; De-Qiang Ji; Hong-Jun Wu; De-Bin Ji (Chemical Engineering Journal, 2026)

Benzo[c]chromene-based light-emitting conjugated polymer for high performance deep-blue PLEDs - Hong Ren; Zhiyang Sun; Xiang An; Qian Wu; Xinyu Du; Xiaoqi Guo; Wenyu Chen; Mengyuan Li; Jiabin Liu; Dunliang He; Ning Sun; Lubing Bai; et al. (Chemical Engineering Journal, 2026)

Multi-scenario simulation and driving mechanisms of carbon storage under urban expansion: a case study of the alluvial/sedimentary sand land in the ancient course of the Yellow River - Xuejian Sun; Guodong Li; Xiaojuan Ren; Man Zhang; Jingyu Wang; Qingtao Zhao; Longsheng Wang; Yunfei Gong (Modeling Earth Systems and Environment, 2026)

Hop bitter acids from the pistillate flower of Humulus lupulus L. and their anti-inflammatory and anti-dengue virus activities - Biao Sun; Yun-Lin Ao; Xia Cao; Jia-Bing Zhang; Xia Zhang; Dong-Hao Lu; Man Lin; Jun-Shan Liu; Xiao-Qi Zhang (Phytochemistry, 2026)

Molecular insights into the temperature-responsive interfacial properties of sodium oleate–based combined collectors for spodumene flotation - Ying Zhang; Yuhua Wang; Ning Sun; Man Cui (Minerals Engineering, 2026)

The effects of β-lactoglobulin-puerarin interaction on the properties of protein hydrogels - Peng Man; Lina Sun; Jinghua Pei; Xiue Han; Huajiang Zhang; Haowei Ren (International Dairy Journal, 2026)

Construction of carboxymethyl chitosan/oxidized Astragalus polysaccharide cross-linked gel microspheres in alginate system: Improving the tolerance and functional characteristics of Lactobacillus paracasei - Yilin Sun; Man Zhu; Zimu Li; Xinyan Yang; Wei Zhang; Ling Guo; Yujun Jiang; Yu Zhang (Food Research International, 2026)

From genes to products: High-efficiency biosynthesis and holistic optimization strategies for monounsaturated fatty acids - Lu-Wei Xu; Yan-Cheng Lin; Yi-Ting Shen; Xin Qi; Zi-Xu Zhang; Wang Ma; Xiao-Man Sun (Food Microbiology, 2026)

Ferroptotic stress-guided glutathione dynamics profiling identifies melatonin priming as a potential mesenchymal stem cell strategy for asthma therapy - Hyun Jun Im; Seok Woo Ha; Keunhong Jeong; Jinwon Lee; Chae-Min Ryu; Hyungu Kwon; Jihye Kim; Yi-Xi Gong; HongDuck Yun; YongHwan Kim; Ji-Woong Shin; Hye-Mi Kim; et al. (Chemical Engineering Journal, 2026)

Seasonal study of interactive cascade ventilation: Parametric analysis for energy efficiency and thermal comfort - Haiyang Sun; Han Li; Xiangfei Kong; Zhaoying Wang; Man Fan (Building and Environment, 2026)

Comparison of multi-source merged precipitation products using independent gauge observations - Huiwen Zhang; Lingna Wei; Ying Zhu; Jianhong Zhou; Songyan Liu; Xiaosong Sun; Xiaoqi Kang; Man Gao; Zheng Duan; Wade T. Crow; Jianzhi Dong (Atmospheric Research, 2026)

Curcumin Attenuates Cuproptosis via Activating Autophagy Through Inhibition of the AKT/mTOR/P70S6K-Signaling Pathway in Parkinson’s Disease Models - Feng Ren; Yanpeng Sun; Man Wang; Kun Zheng; Chao Zuo; Hui Shang; Jing Zhu (Molecular Neurobiology, 2026)

Metformin Inhibits Microglial Activation-Mediated Cuproptosis by Modulating the TLR4/Myd88/NF-κB Signaling Pathway in Parkinson’s Disease - Hui Shang; Zihan Wang; Yanpeng Sun; Chao Zuo; Man Wang; Kun Zheng; Yunfu Wang; Jing Zhu (Molecular Neurobiology, 2026)

Dual-nitrogen-source anchored biochar achieves efficient removal of Cr(VI) from wastewater through an adsorption-reduction coupling mechanism - Xue-Qi Fan; Yi-Man Sun; Le Tao; Shu-Xia Guan; De-Bin Ji (Journal of Environmental Chemical Engineering, 2025)

The variation of the East Asian summer monsoon on multi-centennial scale during 8.3–2.9 ka BP - Chao-Jun Chen; Ya-Xi Dong; Yao Wu; Jian Zhang; Hai-Bo Wang; Yan-Xia Xue; Wen-Jun Sun; Man-Ping Xie; Hai Cheng; Jun-Yun Li; Ming-Qiang Liang; Ting-Yong Li (Global and Planetary Change, 2025)

Effect of edible ethanol-induced redistribution of gluten proteins on fresh noodle quality and starch digestibility - Xianyu Cao; Kun Feng; Yishu Wang; Yanfei Wang; Chuanwu Han; Meng Ma; Qingjie Sun; Fengwei Xie; Man Li (Food Chemistry, 2025)

Targeted screening of pancreatic lipase inhibitory peptides from quinoa protein hydrolysates by ligand fishing - Zeyue Fu; Junhao Wang; Chunxiao Wu; Jinfan Qin; Byung-Hoo Lee; Man Li; Qingjie Sun; Wenting Tang (Food Chemistry, 2025)

High-performance edible alginate straws constructed with zein coatings by phase separation and electrostatic assembly after gradient diffusion - Yunpeng Qu; Yuanpu Liu; Kexin Shi; Jiabo Wang; Yanfei Wang; Meng Ma; Qingjie Sun; Fengwei Xie; Man Li (Food Packaging and Shelf Life, 2025)

Self-sacrificing strategy enables amorphous precursor mediated crystallization of phase-pure Na4Fe3(PO4)2P2O7 for advanced sodium-ion batteries - Yan Chen; Yixin Zhang; Yuefeng Su; Zekai Lv; Wei Wang; Sanchao Liu; Wenbin Sun; Meng Wang; Man Xie (Chemical Engineering Journal, 2025)

Gradient lithiophilic metal foam via magnetic sputtering deposition in dendrite free lithium metal anodes - Wenlong Liu; Jianzong Man; Xiaodong Sun; Ning Zhang; Haibang Zhang; Kun Liu; Zhongsheng Wen; Song Li; Juncai Sun (Chemical Engineering Journal, 2025)

Structure characterization of a polysaccharide isolated from sugarcane leaves and its macrophage polarization activity and beneficial effects for cisplatin treatment of lung cancer - Man Zhang; Tong Sun; Xiaoyu Wang; Zhansong Zhang; Shanshan Zhai; Xiaotao Hou; Yuanyuan Hou; Gang Bai (Carbohydrate Polymers, 2025)

Methods and experiments for analysing hard-bottom layer changes and monitoring wheel sink depth in paddy fields - Tuanpeng Tu; Xiwen Luo; Lian Hu; Sun-Ok Chung; Jie He; Runmao Zhao; Pei Wang; Gaolong Chen; Dawen Feng; Mengdong Yue; Zhongxian Man; Md Rejaul Karim; et al. (Computers and Electronics in Agriculture, 2025)

Effect of cooking condiments on swelling and starch-gluten matrix structural/molecular changes of cooked noodles - Wenxin Xie; Peng Wang; Ran Zhao; Kexin Shi; Meng Ma; Yanfei Wang; Qingjie Sun; Man Li; Fengwei Xie (Food Chemistry, 2025)

Using a salt template strategy to prepare rapidly rehydrated dried rice noodles with enhanced qualities - Zhongxiu Wang; Lin Gao; Yang Qin; Man Li; Liu Xiong; Qingjie Sun (Food Chemistry, 2025)

Comparative study on the structural, antioxidant and functional properties of hydrolysates from Pleurotus erynigii and Pleurotus ostreatus protein by alcalase and trypsin - Xiao-Xuan Hou; Shu-Jing Bing; Man Hao; Jie Yang; Gui-Jin Sun; Ying-Qiu Li; Chen-Ying Wang; Yan Liang; Hai-Zhen Mo (Food Bioscience, 2025)

Mechanism of high intensity ultrasonic treatment combined with β-glucan affecting the structure of highland barley protein to improve the stability of highland barley milk - Hongwei Cao; Xiaotong Zhuang; Haojie Liu; Man Wang; Kai Huang; Hongdong Song; Sen Li; Yu Zhang; Zhenliang Sun; Xiao Guan (Food Hydrocolloids, 2025)

Hypervirulent/persistent genotype L. monocytogenes ST87/CC87 contamination in commercial fresh Flammulina velutipes production facility in China - Ruizhen Feng; Man Li; Qifan Sun; Jiayi Cai; Jianheng Cheng; Ying Zhang; Zhiwei Ye; Qingping Wu; Moutong Chen (Food Control, 2025)

Sodiophilic oxygen-vacancy-engineered Cu2O microsheets on Cu foam for dendrite-free Na metal anodes - Xiaodong Sun; Ning Zhang; Wenlong Liu; Jianzong Man; Yehong Du; Juncai Sun (Chemical Engineering Journal, 2025)

Hydrocarbon organic conjugated skeleton with multi-sites functionalization for non-doped ultraviolet organic light-emitting diodes with CIEy = 0.029 - Jing Yang; Jingli Lou; Mingjian Ni; Zhiqiang Zhuo; Hao Li; Xiang An; Ning Sun; Mengyuan Li; Xuehua Ding; Lizhi Wang; Man Xu; Xueqin Ran; et al. (Chemical Engineering Journal, 2025)

Cumulative exposure to the chemical components of PM2.5 and the prevalence of Anemia: Insights from a large group of workers in South China - Xinyue Li; Zhiqiang Li; Yongqing Sun; Man Zhang; Meimei Zhong; Yueqian Wu; Xudan Chen; Xurui Sun; Dan Chen; Huanle Cai; Guanghui Dong; Hui Tang; et al. (Atmospheric Environment, 2025)

Protective effects and mechanisms of Saikosaponin A against myocardial ischemia based on network pharmacology, molecular docking, and experimental validation - Hongyu Wu; Wei Wang; Lintong Wen; Jie Cheng; Yurun Xue; Man Liao; Haoying Li; Xia Li; Jingyi Zhang; Shijiang Sun; Shengjiang Guan (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Long-term ecotoxicological effects of benzophenone-3 on the marine invertebrate, Crepidula onyx: Impacts on bioaccumulation, reproduction, shell integrity, condition indexes, and embryonic and larval development - Leyi Xi; Cheuk Fung Ng; Hei Ching Wong; Chris Kong Chu Wong; Rudolf Shiu Sun Wu; Yiu Fai Tsang; Vengatesen Thiyagarajan; Jill Man Ying Chiu (Journal of Hazardous Materials, 2025)

Boosting biogas prediction: An interpretable SVM-RVM-stacking model for small-sample anaerobic digestion - Yanan Liao; Chuhan Pan; Fulu Lu; Man Sun; Hongguang Zhu (Journal of Environmental Chemical Engineering, 2025)

Effect of oleic acid iodine value on the flotation performance of oleic acid-based collectors for spodumene - Ying Zhang; Ning Sun; Yuhua Wang; Liu Luo; Man Cui; Yu Li (Journal of Environmental Chemical Engineering, 2025)

Rational construction and reaction mechanism of bimetal oxides/carbon nanofibers sorbent for H2S removal at high temperature - Xiaojun Xue; Zidan Li; Ying Yue; Man Zhang; Yangjie Sun; Jie Mi; Jiancheng Wang; Ajay Mishra; Jasur Shodmanov; Yu Feng (Journal of Environmental Chemical Engineering, 2025)

Enhancing the formation rate and level of oat globulin fibrils by microwave heating: Elucidation of potential mechanisms - Mengdi Cai; Hongwei Cao; Sen Li; Hongdong Song; Yu Zhang; Kai Huang; Man Wang; Zhenliang Sun; Xiao Guan (Food Hydrocolloids, 2025)

Centennial-scale evolution, source apportionment, and ecological risks of heavy metals in Daya Bay, South China sea - Xiangtian Man; Jian Sun; Yu Xiang; Hong Su; Honghui Huang; Yangguang Gu; Han Zhang; Richard W. Jordan; Shijun Jiang (Environmental Pollution, 2025)

Impact of cationic reagent structure on the performance of combined collectors in spodumene-feldspar flotation system - Ying Zhang; Yuhua Wang; Ning Sun; Haiqiang Feng; Yu Li; Man Cui (Minerals Engineering, 2025)

Temperature effects on sodium oleate flotation performance and interfacial interactions in spodumene flotation - Ying Zhang; Yuhua Wang; Ning Sun; Man Cui (Journal of Water Process Engineering, 2025)

Influencing the retrogradation properties of potato mash through multi-scale structural modifications mediated by enzymatic hydrolysis forms - Hongwei Cao; Mengting Huang; Zhenhao Liu; Kai Huang; Man Wang; Hongdong Song; Sen Li; Yu Zhang; Zhenliang Sun; Xiao Guan (Food Chemistry, 2025)

Lacuna-mimic human-derived nasal septal chondrocyte clusters encapsulated in click chemistry-based hydrogel for in vivo cartilage regeneration - Jung Ho Jeon; Seo Young Cheon; Sun Hwa Park; Hyunji Lee; Seung-Yeon Yoo; Min Young Ahn; Donghyun Lee; Man Soo Kim; Jeong Hun Park; Scott J. Hollister; Heebeom Koo; Sung Won Kim (Chemical Engineering Journal, 2025)

Additive-free nitrile-based gel polymer electrolytes with enhanced interfacial compatibility for Lithium metal batteries - Yuxue Sun; Man Wang; Xiaorong Zhang; Haiming Xie; Jun Liu (Chemical Engineering Journal, 2025)

Inactivation of Cyclotella meneghiniana to prepare biochar by in-liquid pulsed discharge plasma - Yin Li; Yanbin Xin; Bing Sun; Chenxi Man; Emile Mouele; Leslie Petrik; Bernard Jan Bladergroen; Cheng Zhang (Biomass and Bioenergy, 2025)

Coupled dynamic modeling and analysis for collecting asteroid soil using a flexible brush sampler - Qichen Sun; Bolin Zhang; Bo Lei; Fan Guo; Jianfeng Man; Jinyang Liu; Zeng Zhao (Advances in Space Research, 2025)

Tidal responses of the semi-enclosed Bohai Sea to the long-term expansion of the Yellow River Delta - Jiayue Sun; Man Zhang; Jianjun Zhou (Frontiers in Marine Science, 2025)
River deltas, formed by fluvial sediment accumulation, act as dynamic interfaces between land and sea. The Yellow River Delta (YRD) has prograded rapidly into the semi-enclosed shallow Bohai Sea (BS) over the past century. While tidal dynamics are recognized as key drivers of estuarine morphology and ecology, it is unclear how and to what extent this deltaic expansion impacts the tidal regime in the BS. This study investigates the tidal responses of the BS to both historical (circa 1855, 1962, 1981, 2003) and projected century-scale delta coastline advancement, utilizing numerical simulations and theoretical analysis. The results indicate that the seaward expansion of the delta alters tidal resonance patterns, inducing tidal responses in a nonlinear way across the BS. Specifically, historical delta expansion enhanced tidal flux and currents monotonically across major bays in the BS, whereas future sedimentation over the coming decades leads to an overall reduction in tidal dynamics. Locally, tidal currents and sediment transport capacity are expected to increase around the active lobe owing to river mouth protrusion at the expense of having the river base level raised; they decrease near the abandoned lobes with standby river courses, potentially hindering sediment dispersal and threatening the delta’s morphological stability. Furthermore, the basin-scale tidal weakening caused by the delta expansion may diminish water exchange capacity in the BS, posing challenges for ecological environment and economic services.

Fabrication and application of ferrocene contained MOF derived porous carbon: A single multi-interference clean-up QuEChERS sorbent for facile analysis of triazine herbicides in various fruits and vegetables by LC-MS/MS - Zi-Ling Li; Da-Jin Yang; Jia-Qi Zhao; Wen-Jie Sun; Jie Gao; Shu-Feng Song; Hou-Jun Xu; Hai-Jie Li; Fa-Ming Tian; Man-Man Wang (Food Chemistry, 2025)

Advances in multi-omics technologies for identifying metabolic engineering targets and improving lipid production in microalgae - Chun-xiao Yan; Shuai Zhang; Lu-wei Xu; Han Gao; Zi-xu Zhang; Wang Ma; Xiao-man Sun (Bioresource Technology, 2025)

Site aridity has a stronger impact on nocturnal sap flow than species with contrasting stomatal behaviors on the northeastern Tibetan Plateau - Fang Wang; Junzhou Zhang; Xiaohua Gou; Zhaoyong Hu; Fen Zhang; Zihong Man; Qipeng Sun; Min Xu; Patrick Fonti (Agricultural and Forest Meteorology, 2025)

Two new acorane-type sesquiterpenoids from an endophytic Trichoderma harzianum associated with Paeonia lactiflora Pall - Yun-Peng Sun; Man-Li Zhang; Yang Yu; Ran Sun; Si-Rui Wang; Jin-Song Liu; Guo-Kai Wang (Natural Product Research, 2025)

Modeling and control method of coal instability around cavity under water jet impact loading - Man Yuan; Shuaibin Sun; Yingke Liu; Tengrui Yang; Chao Li; Yue Niu; Xiaojiang Wen (Tunnelling and Underground Space Technology, 2025)

Long-term exposure to dust in fine particulate matter and post-stroke functional impairment—Findings from the China National Stroke Screening Surveys - Zhaoyang Pan; Xueyan Han; Man Cao; Ruohan Wang; Jian Guo; Wei Sun; Jiarun Mi; Yuanli Liu; Tao Xue; Tianjia Guan (Journal of Hazardous Materials, 2025)

Effects of combination of UV-B irradiation and drying on the physicochemical properties of key components and processing quality of germinated whole wheat flour - Ting Wei; Wentong Liu; Jiahao Huang; Na Ji; Qingjie Sun; Man Li; Meng Ma; Fengwei Xie (Journal of Cereal Science, 2025)

Rice bran protein fibril and chitin nanofiber complexes as a new material for fat substitution and saltiness enhancement - Yao Feng; Yu Zhang; Kai Huang; Sen Li; Hongwei Cao; Pengxiao Zhang; Man Wang; Zhenliang Sun; Xiao Guan (Food Chemistry, 2025)

Applicability analysis of different evapotranspiration models for maize farmland in the lower Yellow River Plain based on eddy covariance measurements - Xiaojuan Ren; Guodong Li; Shengyan Ding; Jingyu Wang; Man Zhang; Xuejian Sun; Qingtao Zhao; Pengfei Li (Ecohydrology & Hydrobiology, 2025)

Biogas slurry-derived hierarchical hollow carbon spheres with high microporosity for efficient hydrogen storage - Hang Yuan; Longlong Lei; Hongguang Zhu; Jie Ma; Fanghui Pan; Man Sun (Chemical Engineering Journal, 2025)

Evaluation of the efficacy and safety of omega-3 fatty acid nutritional supplements from Schizochytrium sp. in dog food - Zi-Xu Zhang; Yan-Cheng Lin; Min Lian; Ying-Feng Li; Jin-Fa Chen; Xue-Lian Ma; Dong-Sheng Guo; Guang Yang; Xiao-Man Sun (Algal Research, 2025)

Effectively mitigated eutrophication risk by strong biological carbon pump (BCP) effect in karst reservoirs - Wenke Zhang; Wanfa Wang; Sen Xu; Qingqing Sun; Wenhong Shi; Jiayi Man; Shengde Yu; Yujing Yang; Wenxin Wu; Xia Hu; Qixin Wu; Pan Wu; et al. (Water Research, 2025)

Iodine crystallization-promoted efficient capture of iodine by nonporous covalent organic polymer - Yong Man; Xiaoshuang Cui; Ruobing Wang; Shiqi Chai; Chenchen Song; Yaming Sun; Renyong Zhao; Lijun He (Journal of Hazardous Materials, 2025)

Harnessing microalgae: Pioneering strategies for cost-effective EPA synthesis - Yi-Ting Shen; Zi-Xu Zhang; Xin Qi; Hong-Xuan Wu; Yan-Cheng Lin; Wang Ma; Guang Yang; Xiao-Man Sun (Food Bioscience, 2025)

Cell wall engineering of Yarrowia lipolytica to improve extraction efficiency of functional lipids - Feng Zhang; Yi Zheng; Hong-Yan Jing; Fei Du; Yi-Wen Hang; Zi-Xu Zhang; Wang Ma; Xiao-Man Sun (Food Bioscience, 2025)

Peppermint essential oil: Disruption of cellular structure and function in Listeria monocytogenes - Chun-Ling Yang; Man Hao; Jie Yang; Gui-Jin Sun; Ying-Qiu Li; Chen-Ying Wang; Yan Liang (Food Bioscience, 2025)

The role of cognitive elements plays in physical activity interventions among individuals with attention-deficit/hyperactivity disorder: A systematic review of brain evidence - Yuan Fang; Fenghua Sun; Zixin Wang; Yaxi Yang; Man Lau; Kunyi Huang; Michael Kin-Chung Yeung; Simon B. Cooper; Yajun Chen (Brain Imaging and Behavior, 2025)

Microwave-assisted in-situ growth and performance promotion via the synergistic effect of ZnCoY tri-metal oxides (Y = Fe, Cu, Ni)/carbon nanofibers sorbent for H2S removal - Man Zhang; Xiaojun Xue; Yangjie Sun; Rongrong Jin; Jie Mi; Jiancheng Wang; Yu Feng (Chemical Engineering Journal, 2025)

Interaction of starch nanoparticles with digestive enzymes and its effect on the release of polyphenols in simulated gastrointestinal fluids - Jie Yang; Yujing Sun; Xuyan Dong; Man Li; Yang Qin; Lei Dai; Qingjie Sun (Food Chemistry, 2025)

Prediction of non-Newtonian rheology in anaerobic co-digestion: Substrate mixing ratio effects on consistency and shear thinning characteristic - Yanan Liao; Man Sun; Fulu Lu; Qi Wu; Hongguang Zhu (Chemical Engineering Journal, 2025)

Tailored large-particle quantum dots with high color purity and excellent electroluminescent efficiency - Bo-Chen Liu; Qizhong Lin; Shuang-Qiao Sun; Qi Sun; Xing Peng; Xinyuan Chen; Yang Li; Yue-Min Xie; Shuit-Tong Lee; Man-Keung Fung (Science Bulletin, 2025)

Spatial‒temporal pattern of primary productivity in the South China Sea under the monsoon regulation: Insights from observations of 2003–2022 - Xingda Chen; Jinyue Chen; Shuisen Chen; Chongyang Wang; Yishan Sun; Guangjia Jiang; Man Wu; Jian Li (Marine Environmental Research, 2025)

Removal of ciprofloxacin by PAA-PAM hydrogel: Adsorption performance and mechanism studies - Man Gao; Mengmeng Sun; Jingtao Bi; Shizhao Wang; Xiaofu Guo; Fei Li; Jie Liu; Yingying Zhao (Journal of Water Process Engineering, 2025)

Structure-phase transformation of bismuth oxide to BiOCl/Bi24O31Cl10 shoulder-by-shoulder heterojunctions for efficient photocatalytic removal of antibiotic - Man Yang; Zhenzhen Shi; Shaodong Sun; Bian Yang; Jie Cui; Jianing Li; Daqin Yun; Nian Lei (Journal of Environmental Sciences, 2025)

Curdlan inclusion modifies the rheological properties and the helix-coil transition behavior of gelatin and increases the flexibility of gelatin films - Xinyu Sun; Yongxin Liu; Xinyi Li; Liya Chen; Man Li; Qingjie Sun; Fenghuan Wang; Jun Hao; Fengwei Xie; Yanfei Wang (Food Chemistry, 2025)

An antimicrobial and adhesive conductive chitosan quaternary ammonium salt hydrogel dressing for combined electrical stimulation and photothermal treatment to promote wound healing - Qiaoyu Huang; Yong Hu; Yige Chen; Man Zhou; Yuhong Zhang; Zhengguang Sun; Zhaoxia Chen (Carbohydrate Polymers, 2025)

Exploring the influence of lysine incorporation on the physicochemical properties of quinoa protein gels formed under microwave versus conventional heating conditions - Hongwei Cao; Xiaoxue Wang; Weibin Wu; Man Wang; Yu Zhang; Kai Huang; Hongdong Song; Zhenliang Sun; Xiao Guan (Food Research International, 2025)

Effects of sodium chloride on the textural attributes, rheological properties, microstructure, and 3D printing performance of rice starch-curdlan composite gel - Weixian Li; Kangning Zhang; Yang Qin; Man Li; Hongyan Li; Minqiang Guo; Tongcheng Xu; Qingjie Sun; Na Ji; Fengwei Xie (Food Chemistry, 2025)

Characterization and application of Schizochytrium sp. HX-308 promoters for enhanced docosahexaenoic acid biosynthesis - Chun-Xiao Yan; Yi Zheng; Shuai Zhang; Zi-Jia Li; Zi-Xu Zhang; Ying-Shuang Xu; Wang Ma; Xiao-Man Sun (Food Bioscience, 2025)

Coupling ultrasound and low temperature stress for enhancing Docosahexaenoic acid production in Schizochytrium sp. - Chun-Xiao Yan; Shuai Zhang; Kai-Nan Zhang; Fei Du; Wang Ma; Xiao-Man Sun (Food Bioscience, 2025)

Can cadmium-contaminated rice be used to produce food additive sodium erythorbate? - Lei Sun; Xiaoju Zhang; Yanzheng Zhou; Zhen Peng; Fengjie Cui; Qiang Zhou; Zaiwei Man; Jing Guo; Wenjing Sun (Food Chemistry, 2025)

Deciphering the distinct roles of polyketide synthase subunits in polyunsaturated fatty acid and lipid accumulation in Schizochytrium sp. - Hong-Xuan Wu; Wen-Qian Yang; Zi-Xu Zhang; Yan-Cheng Lin; Wang Ma; Xiao-Man Sun; He Huang (Food Bioscience, 2025)

A food for elders with dysphagia: Effect of sodium alginate with different viscosities on the gel properties of antarctic krill composite shrimp surimi - Yuting Tan; Peizi Sun; Xinyu Zhang; Huihui Zhang; Hao Man; Dongmei Li (Food Hydrocolloids, 2025)

H-zeolite supported multi-interface metal catalysts for the catalytic destruction of chlorinated organics - Pengfei Sun; Si Chen; Man Xie; Lujun Cheng; Jiasheng Wang; Fan Dong; Xiaoping Dong; Xiaole Weng (Chemical Engineering Journal, 2025)

YTHDF2 promotes arsenic-induced malignant phenotypes by degrading PIDD1 mRNA in human keratinocytes - Qian Zhang; Jin Man; Tianhe Zhao; Donglei Sun; Zunzhen Zhang (Chemico-Biological Interactions, 2025)

Highly-efficient co-production of microbial lipid and magnesium ammonium phosphate from N-acetyl-D-glucosamine - Wei Zhou; Yanan Wang; Wenting Zhou; Yi Gao; Man Zhao; Shuqi Sun; Binglei Lu; Hong Chen; Weiyi Yang; Yifan Qi; Zhiwei Gong (Bioresource Technology, 2025)

Effect of Post-transplant Dietary Restriction on Hematopoietic Reconstitution and Maintenance of Reconstitution Capacity of Hematopoietic Stem Cells - Si Tao; Xingxing Qiu; Yiting Wang; Rongrong Qiu; Chenghui Yu; Man Sun; Lulu Liu; Zhendong Tao; Liu Zhang; Duozhuang Tang (Stem Cell Reviews and Reports, 2025)
Hematopoietic cell transplantation (HCT) is an important therapy for many hematological malignancies as well as some non-malignant diseases. Post-transplant hematopoiesis is affected by multiple factors, and the mechanisms of delayed post-transplant hematopoiesis remain poorly understood. Patients undergoing HCT often suffer from significantly reduced food intake due to complications induced by preconditioning treatments. Here, we used a dietary restriction (DR) mouse model to study the effect of post-transplant dietary reduction on hematopoiesis and hematopoietic stem cells (HSCs). We found that post-transplant DR significantly inhibited both lymphopoiesis and myelopoiesis in the primary recipient mice. However, when bone marrow cells (BMCs) from the primary recipient mice were serially transplanted into secondary and tertiary recipient mice, the HSCs derived from the primary recipient mice, which were exposed to post-transplant DR, exhibited a much higher reconstitution capacity. Transplantation experiments with purified HSCs showed that post-transplant DR greatly inhibited hematopoietic stem cell (HSC) expansion. Additionally, post-transplant DR reshaped the gut microbiotas of the recipient mice, which inhibited inflammatory responses and thus may have contributed to maintaining HSC function. Our findings may have important implications for clinical work because reduced food intake and problems with digestion and absorption are common in patients undergoing HCT. Graphical Abstract

Formation tracking control for networked heterogeneous MSV systems with actuator faults: A distributed optimal event-triggered fixed-time sliding mode fault-tolerant control approach - Siyuan Wang; Man Zhu; Yuanqiao Wen; Wuqiang Sun; Weidong Zhang; Tao Lei (Ocean Engineering, 2024)

YTHDF2 phase separation promotes arsenic-induced keratinocyte transformation in a poly-m6A-dependent manner by inhibiting translational initiation of the key tumor suppressor PTEN - Tianhe Zhao; Wenxiao Xiong; Jingsilin Cai; Qian Zhang; Donglei Sun; Keyan Long; Jin Man; Zunzhen Zhang (Journal of Hazardous Materials, 2024)

Change of morphology of rice derived spherical hydrochar during activation - Shuaizhi Man; Kai Sun; Shu Zhang; Mengjiao Fan; Xun Hu (Journal of Environmental Chemical Engineering, 2024)

Atmosphere-driven oriental regulation of Ru valence for boosting alkaline water electrolysis - Na Xu; Man-Man Li; Hai-Yi Sun; Guodong Li; Xin Wen; Denghao Ouyang; Chun-Ying Liu; Yong-Ming Chai; Bin Dong (Chemical Engineering Journal, 2024)

Cavity-modulated visualization of dual magnetic coupling behavior for multifunctional Co/DMAOP composites - Man Li; Xiao Li; Jieyan Zhang; Haowei Zhou; Zhenfa Yu; Chao Li; Moustafa Adel Darwish; Tao Zhou; Shi-Kuan Sun; Di Zhou (Chemical Engineering Journal, 2024)

Aberrant DNA Methylation Profile of Dickkopf-1 in Ankylosing Spondylitis - Xiaoya Sun; Yujie Deng; Man Ni; Tao Zhang; Xinqi Wang; Ye Wu; Zongwen Shuai; Faming Pan (Biochemical Genetics, 2024)

Identification of major histocompatibility complex II gene in Pampus argenteus and the expression pattern in Pampus argenteus kidney cell line under the pathogen stress - Youyi Zhang; Jiabao Hu; Yuanbo Li; Weiwei Gu; Zukang Feng; Kaiheng Yan; Man Zhang; Yaya Li; Zi Yuan; Xiaomei Sun; Lu Zhang; Shanliang Xu; et al. (Aquaculture, 2024)

Corrigendum to “Association of urban green space with metabolic syndrome and the role of air pollution” [Landsc. Urban Plann. 248 (2024) 105100] - Yi Sun; Yunli Chen; Yuanyuan Huang; Yan Luo; LiPing Yan; Sailimai Man; Canqing Yu; Jun Lv; Chuangshi Wang; Jun Wu; Heling Bao; Bo Wang; et al. (Landscape and Urban Planning, 2024)

Microwave heating intensified in-situ preparation of ZnO-based desulfurization sorbent with multi-stage structure and promoted performance - Yangjie Sun; Wenjian Feng; Man Zhang; Ying Yue; Jie Mi; Liping Chang; Jiancheng Wang; Yu Feng (Journal of Cleaner Production, 2024)

Functionalized construction of multiple active centers for durability controlling during catalytic combustion of chlorinated aromatic hydrocarbons - Lujun Cheng; Si Chen; Man Xie; Lu Fang; Pengfei Sun; Fan Dong; Xiaoping Dong (Chemical Engineering Journal, 2024)

Response Mechanism of Dynamic Tensile Mechanics in Granite Under Microwave Irradiation: Insights from Experiments and Simulations - Bo-Wen Sun; Sheng-Qi Yang; Man Huang; Heng Li; Wen-Ling Tian; Yan-Hua Huang (Rock Mechanics and Rock Engineering, 2024)

Effect of government environmental attention on green transformation: Empirical analysis from a spatiotemporal perspective in China - Haojie Man; Yueyue Sun; Xinyu Wang; Zhuangyan Qin; Shuangwen Chen; Jianbin Chen (Journal of Cleaner Production, 2024)

Non-radical activation of persulfate by CuO catalyst for degradation of antibiotics - Huajun Xu; Yaning Zhang; Xinting Liu; Man Xie; Meixuan Wu; Shengyu Shao; Baocheng Zhou; Pengfei Sun; Xiaoping Dong (Journal of Environmental Chemical Engineering, 2024)

The changes in HMOs of GDM mothers over lactation: Regulation on the gut microbiota development in offspring - Lina Zhang; Jinyue Zhang; Yalu Yan; Sufang Duan; Xuemin Wang; Ignatius Man-Yau Szeto; Jun Liu; Zhaona Sun; Xiang Feng; Kasper Hettinga; Peng Zhou (Food Bioscience, 2024)

Mechanism of Lacticaseibacillus rhamnosus JY027 alleviating hyperuricemia in mice through gut-kidney axis - Chao Miao; Kai Dong; Yu Shen; Yilin Sun; Wenyan Li; Chaoxin Man; Yu Zhang; Qianyu Zhao; Yujun Jiang (Food Bioscience, 2024)

Drug evaluation platform based on non-destructive and real-time in situ organoid fate state monitoring by graphene field-effect transistor - Meng Tian; Jinsong Wei; Enguang Lv; Chonghui Li; Guofeng Liu; Yang Sun; Wen Yang; Qingzhe Wang; Congcong Shen; Chao Zhang; Baoyuan Man; Jihua Wang; et al. (Chemical Engineering Journal, 2024)

Strong, anti-swelling, and biodegradable seaweed-based straws with surface mineralized CaCO3 armor - Yuanpu Liu; Wen Peng; Ting Wei; Yajie Yuan; Xianyu Cao; Meng Ma; Qingjie Sun; Man Li; Fengwei Xie (Carbohydrate Polymers, 2024)

Phytochemical and chemotaxonomic investigations on the fruit parts of Illicium verum Hook. f - Man Li; Pengcheng Yang; Mei Jin; Tieqiang Zong; Junnan Li; Sainan Li; Long Jin; Jinfeng Sun; Shengbao Diao; Wei Zhou; Gao Li (Biochemical Systematics and Ecology, 2024)

High-Speed Clearing and High-Resolution Staining for Analysis of Various Markers for Neurons and Vessels - Jung Min Park; Seock Hwan Choi; Eun-Shil Lee; Sang-Il Gum; Sungkuk Hong; Dong Sun Kim; Man-Hoon Han; Soung-Hoon Lee; Ji Won Oh (Tissue Engineering and Regenerative Medicine, 2024)

Effects of N rhizodeposition on rhizosphere N transformation in clonal ramets of Moso bamboo forest - Man Shi; Weiwei Yang; Junbo Zhang; Jilei Sun; Hangxiang Ji; Quan Li; Tingting Cao; Zhikang Wang; Chao Zhang; Xinzhang Song (Plant and Soil, 2024)

Prognostic Significance of Methyl-CpG Binding Domain4 Polymorphism rs140693 and Clinical Characteristics in Chinese Lung Cancer Patients - Zhengxing Li; Yuewen Hu; Chang Xu; Zixiu Zou; Zhenyu Sun; Zhunyi Gao; Man Xiao; Shicheng Guo; Yi Wang; Haijian Wang; Zhiping Wang; Qiang Li; et al. (Phenomics, 2024)

Temporal and spatial evolution of wildfires during the Jurassic: From regional to global scale - Wenxu Du; Dawei Lv; Zhihui Zhang; Man Lu; Dieter Uhl; Munira Raji; Luojing Wang; Aocong Zhang; Yuzhuang Sun; Tiantian Wang; Dongdong Wang (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Polystyrene nanoplastics induce lipophagy via the AMPK/ULK1 pathway and block lipophagic flux leading to lipid accumulation in hepatocytes - Zhuying Fan; Yukang Zhang; Yuting Fang; Huiyuan Zhong; Tingting Wei; Huraira Akhtar; Jiahuai Zhang; Man Yang; Yanbo Li; Xianqing Zhou; Zhiwei Sun; Ji Wang (Journal of Hazardous Materials, 2024)

Multicolor luminescence of carbon Dots: From mechanisms to applications - Man Jiang; Yuzhu Sun; Mingyue Chen; Hongfei Ji; Ying Liu; Ruijie Qin; Xiyan Li; Hongling Gao; Ruizhong Zhang; Libing Zhang (Chemical Engineering Journal, 2024)

Oceanic euxinia and seafloor oxygenation linked to continental weathering and influxes during the Late Devonian Frasnian–Famennian bio-crisis and Annulata bio-event - Jian Chen; YueHan Lu; YongGe Sun; Nicholas Hogancamp; Man Lu (Chemical Geology, 2024)

MiRNA-133a-3p Attenuates Renal Tubular Epithelial Cell Injury via Targeting MALM1 and Suppressing the Notch Signaling Pathway in Diabetic Nephropathy - Yuting Li; Peng Tan; Qianpan Liu; Man Liu; Yue Wang; Weixin Kong; Huaixin Sun; Xiang Shao (Cell Biochemistry and Biophysics, 2024)

Effects of herbal formula on growth performance, apparent digestibility, antioxidant capacity, and rumen microbiome in fattening lambs under heat stress - Dongyao Su; Lianjie Song; Qing Dong; Ao Zhang; Lu Zhang; Yanan Wang; Man Feng; Xuemei Li; Feng Li; Xinsheng Sun; Yuhong Gao (Environmental Science and Pollution Research, 2024)

The complexity of structural variations in Brassica rapa revealed by assembly of two complete T2T genomes - Yifan Zhou; Hanzhe Ye; Enwei Liu; Jingjing Tian; Liping Song; Zhiyong Ren; Man Wang; Zhenghui Sun; Liguang Tang; Zhongyue Ren; Jinquan Li; Qijun Nie; et al. (Science Bulletin, 2024)

Association of urban green space with metabolic syndrome and the role of air pollution - Yi Sun; Yunli Chen; Yuanyuan Huang; Yan Luo; LiPing Yan; Sailimai Man; Canqing Yu; Jun Lv; Chuangshi Wang; Jun Wu; Heling Bao; Bo Wang; et al. (Landscape and Urban Planning, 2024)

Degradable tumor-specific H2S nanogenerators for disrupting tumor metabolic symbiosis and activating anti-tumor immune responses - Qianqian Sun; Man Wang; Yanrong Qian; Luying Qiao; Chunxia Li (Chemical Engineering Journal, 2024)

Isophorone-based crystallization-induced-emission sensors detect proteome aggregation in live cells and tissues with breast cancer - Xiaomeng Jia; Di Shen; Jintai Deng; Kainan Wang; Xueqing Wang; Yijin Guo; Lu Sun; Hao Jin; Qiuxuan Xia; Huan Feng; Biao Jing; Jialu Sun; et al. (Analytica Chimica Acta, 2024)

Astaxanthin Rescues Memory Impairments in Rats with Vascular Dementia by Protecting Against Neuronal Death in the Hippocampus - Na Wei; Luo-man Zhang; Jing-Jing Xu; Sheng-lei Li; Rui Xue; Sheng-li Ma; Cai Li; Miao-miao Sun; Kui-sheng Chen (NeuroMolecular Medicine, 2024)

The A subunit of vacuolar H+-ATPase gene (CmVHA-A) plays opposite roles in plant growth and drought tolerance of chrysanthemum under different growing conditions - Yan-Hong Liu; Zhen-Hao Zou; Man-Man Zhang; Zhang-Ji Guan; Lian-Da Du; Da-Gang Hu; Cheng-Shu Zheng; Cui-Hui Sun (Plant Science, 2024)

Based on hydrogen and disulfide-mediated bonds, l-lysine and l-arginine enhanced the gel properties of low-salt mixed shrimp surimi (Antarctic krill and Pacific white shrimp) - Hao Man; Peizi Sun; Junxin Lin; Xiang Ren; Dongmei Li (Food Chemistry, 2024)

Erratum to: Cholesterol homeostasis regulated by ABCA1 is critical for retinal ganglion cell survival - Jialiang Yang; Yuhong Chen; Tongdan Zou; Bai Xue; Fang Yang; Xiangzhou Wang; Yibo Huo; Boyun Yan; Yuxia Xu; Shiyu He; Yi Yin; Jing Wang; et al. (Science China Life Sciences, 2024)

Association of Exposure to Heavy Metal Mixtures with Systemic Immune-Inflammation Index Among US Adults in NHANES 2011–2016 - Xiaoya Sun; Yujie Deng; Lanlan Fang; Man Ni; Xinqi Wang; Tao Zhang; Yuting Chen; Guoqi Cai; Faming Pan (Biological Trace Element Research, 2024)

Eco-friendly drinking straws: Navigating challenges and innovations - Yuanpu Liu; Na Li; Xuyang Zhang; Ting Wei; Meng Ma; Qingjie Sun; Man Li; Fengwei Xie (Trends in Food Science & Technology, 2024)

Nitric oxide-mediated regulation of Aspergillus flavus asexual development by targeting TCA cycle and mitochondrial function - Kunlong Yang; Yue Luo; Tongzheng Sun; Han Qiu; Qingru Geng; Yongxin Li; Man Liu; Nancy P. Keller; Fengqin Song; Jun Tian (Journal of Hazardous Materials, 2024)

Recent advances in the bovine β-casein gene mutants on functional characteristics and nutritional health of dairy products: Status, challenges, and prospects - Yilin Sun; Yixin Ding; Biqi Liu; Jinfeng Guo; Yue Su; Xinyan Yang; Chaoxin Man; Yu Zhang; Yujun Jiang (Food Chemistry, 2024)

Effect of complex prebiotics on Lactobacillus gasseri JM1 fermented soymilk: Physicochemical, flavor characteristics, and metabolites - Yaping Zheng; Wenfang Wu; Man Zhu; Yilin Sun; Dong Hu; Yujun Jiang; Yu Zhang; Chaoxin Man (Food Bioscience, 2024)

Enhancing hydrological extremes prediction accuracy: Integrating diverse loss functions in Transformer models - Xue Li; Qi-Liang Sun; Yanfei Zhang; Jian Sha; Man Zhang (Environmental Modelling & Software, 2024)

Identification of candidate genes for Fusarium head blight resistance from QTLs using RIL population in wheat - Mingxia Zhang; Peng Jiang; Qun Wu; Xu Han; Junxia Man; Junsheng Sun; Jinlong Liang; Jingchuan Chen; Qi Zhao; Ying Guo; Yanrong An; Haiyan Jia; et al. (Plant Molecular Biology, 2024)

Expert Consensus on Big Data Collection of Skin and Appendage Disease Phenotypes in Chinese - Shuang Zhao; Zhongling Luo; Ying Wang; Xinghua Gao; Juan Tao; Yong Cui; Aijun Chen; Daxing Cai; Yan Ding; Heng Gu; Jianying Gu; Chao Ji; et al. (Phenomics, 2024)

Adult hair follicle stem cells differentiate into neuronal cells in explanted rat intestinal tissue - Zuyin Sun; Jiashi Huo; Yongshen Tian; Mei Liu; Yan Liu; Man Xu; Qiyou Yin (In Vitro Cellular & Developmental Biology - Animal, 2024)

LncRNA KCNQ1OT1/miR-496/HMGB1 Signaling Axis Promotes Invasion and Migration of Non-small Cell Lung Cancer Cells - Yan Wang; Xiao-yun Jiang; Man-ying Qu; Jie Liang; Jia-sheng Yang; Rui-lin Sun (Biochemical Genetics, 2024)

Nitrogen fertilization practices alter microbial communities driven by clonal integration in Moso bamboo - Tingting Cao; Man Shi; Junbo Zhang; Hangxiang Ji; Xiao Wang; Jilei Sun; Zhenxiong Chen; Quan Li; Xinzhang Song (Science of The Total Environment, 2024)

Simple and rapid ionic liquid-based one-, two-, three-phase transition microextraction for efficient extraction of trace organic pollutants and elimination of lipid co-extractives from fatty food matrices - Yong Man; Zhen Yang; Yaming Sun; Wenjie Zhao; Guoqiang Xiang; Lijun He (Food Chemistry, 2024)

Over 30% external quantum efficiency for doping-free D-A-type thermally activated delayed fluorescence organic light-emitting diodes - Yang Li; Yixia Liu; Yang Gao; Kai Zhang; Yan-Qiu Sun; Lei Ding; Man-Keung Fung; Jian Fan (Chemical Engineering Journal, 2024)

Evaluation of benefits and risks of immunosuppressive drugs in biomaterial-based neural progenitor cell transplantation for spinal cord injury repair - Bo Guo; Xinhao Zhao; Yunlong Zou; Xiaokang Cheng; Zheng Sun; Xiaoyu Xue; Man Yin; Chen Jin; Zhenni Chen; Rui Quan; Wenbin Liu; Bin Chen; et al. (Chemical Engineering Journal, 2024)

Breathable and washable MXene@gallic acid cross-linked textile assisted by borax for personal multi-protection wearables - Biaobiao Yan; Xiaoting Liao; Tianlei Sun; Leilei Wu; Zhenfei Guo; Man Zhou; Yuanyuan Yu; Qiang Wang; Chaobin He; Ping Wang (Chemical Engineering Journal, 2024)

In-situ curing poly(N,N'-Methylenebisacrylamide)-based composite electrolyte reinforced with high-strength glass fiber skeleton for solid state lithium ion batteries - Yuxiang Zhang; Shijie Lu; Zhikun Zhao; Xinyu Zhang; Haijian Lv; Zhuolin Yang; Wenbin Sun; Man Xie; Daobin Mu (Chemical Engineering Journal, 2024)

On the investigation of composite cooling/heating set gel systems based on rice starch and curdlan - Jing Wang; Qianhui Ma; Pingxiong Cai; Xinyu Sun; Qingjie Sun; Man Li; Yanfei Wang; Lei Zhong; Fengwei Xie (Food Chemistry, 2024)

Ambient temperature anomalies induce electrocardiogram abnormalities: Findings from a nationwide longitudinal study - Jian Guo; Tao Xue; Man Cao; Xueyan Han; Zhaoyang Pan; Dengmin Huang; Wei Sun; Jiarun Mi; Yuanli Liu; Tianjia Guan (Environmental Research, 2024)

Potential scalable fabrication of high-performance photothermal fabric via chemical dyeing for solar-powered brine distillation - Deng Lin; Man Yang; Qiuhan Sun; Xiaoyan Tang; Jingye Li; Hongjuan Ma; Bowu Zhang (Desalination, 2024)

Enhanced fatty acid storage combined with the multi-factor optimization of fermentation for high-level production of docosahexaenoic acid in Schizochytrium sp. - Yu-Lei Jia; Ying Zhang; Lu-Wei Xu; Zi-Xu Zhang; Ying-Shuang Xu; Wang Ma; Yang Gu; Xiao-Man Sun (Bioresource Technology, 2024)

Four uncommon cycloamphilectane-type diterpenoids with antibacterial activity from the South China Sea soft coral Sinularia brassica - Zi-Yi Xia; Man-Man Sun; Yang Jin; Ming-Zhi Su; Song-Wei Li; Hong Wang; Yue-Wei Guo (Phytochemistry, 2024)

N6-methyladenosine promotes aberrant redox homeostasis required for arsenic carcinogenesis by controlling the adaptation of key antioxidant enzymes - Tianhe Zhao; Donglei Sun; Keyan Long; Wenxiao Xiong; Jin Man; Qian Zhang; Zunzhen Zhang (Journal of Hazardous Materials, 2024)

Nickel foam based monolithic catalyst supporting transition metal oxides for toluene combustion: Experimental and theoretical study of interfacial synergistic oxidation and water resistance - Pengfei Sun; Lujun Cheng; Si Chen; Man Xie; Fan Dong; Xiaoping Dong (Chemical Engineering Journal, 2024)

Oxidative Stress Induced by Arsenite is Involved in YTHDF2 Phase Separation - Jin Man; Qian Zhang; Tianhe Zhao; Donglei Sun; Weilian Sun; Keyan Long; Zunzhen Zhang (Biological Trace Element Research, 2024)

Role of KOH-activated biochar on promoting anaerobic digestion of biomass from Pennisetum gianteum - Qing-Hua Liu; Hong-Ying Sun; Zhi-Man Yang (Journal of Environmental Management, 2024)

Integration of genetic engineering and multi-factor fermentation optimization for co-production of carotenoid and DHA in Schizochytrium sp - Zi-Xu Zhang; Lu-Wei Xu; Ying-Shuang Xu; Jin Li; Wang Ma; Xiao-Man Sun; He Huang (Bioresource Technology, 2024)

Two new thymol derivatives from Eupatorium fortunei - Jing Shi; Yan-peng Dai; Min Yuan; Xiao-man Sun; Chuan-jie Song; Yu-guo Liu (Natural Product Research, 2024)

Discrepancies in life cycle assessment applied to concrete waste recycling: A structured review - Xiaoyi Liu; Vahid Asghari; Chor-Man Lam; Shu-Chien Hsu; Dongxing Xuan; Sérgio Cirelli Angulo; Vanderley M. John; Anusha S. Basavaraj; Ravindra Gettu; Jianzhuang Xiao; Chi-Sun Poon (Journal of Cleaner Production, 2024)

Stable carbon isotopes and stomatal frequency of Middle Jurassic ginkgophyte fossils from the Turpan basin, northwestern China: Implications for reconstructing paleo-CO2 changes - Liang Xiao; Jia-qi Liang; Li-yan Guo; De-shuang Ji; Man Yuan; Xiang-chuan Li; Nan Sun; Zuo-chen Li (Journal of Asian Earth Sciences, 2024)

Effect of sheeting stress and heating on the molecular chain structure, size, and conformation of gluten proteins during noodle processing - Mengli Zhang; Ruobing Jia; Meng Ma; Qingjie Sun; Man Li; Fengwei Xie (Food Hydrocolloids, 2024)

Facile synthesis of bead-chain structured MWCNTs@CeO2 with oxygen vacancies-rich for promoting electrochemical energy storage - Xiao-Man Cao; Jia-Qi Chen; Xin-Rui Zhao; Hao Ge; Daliang Liu; Qiong Wu; Zhi-Jia Sun; Qingguo Zhang (Chemical Engineering Journal, 2024)

Porcine β-defensin-2 alleviates aflatoxin B1 induced intestinal mucosal damage via ROS-Erk1/2 signaling pathway - Qinghao Li; Man Zhang; Juan Sun; Yilei Li; Shaopo Zu; Yuqiang Xiang; Xin Jin (Science of The Total Environment, 2023)

Biochar reduces uptake and accumulation of polycyclic aromatic hydrocarbons (PAHs) in winter wheat on a PAH-contaminated soil - Jinfeng WANG; Huanyu BAO; Yu Bon MAN; Jun CAI; Jia LI; Benhua SUN; Fuyong WU (Pedosphere, 2023)

Formononetin attenuates high glucose-induced neurotoxicity by negatively regulating oxidative stress and mitochondrial dysfunction in Schwann cells via activation of SIRT3 - Wen Jiang; Ting Hu; Chen Ye; Man Hu; Qingqing Yu; Lijuan Sun; Jichao Liang; Yong Chen (Food and Chemical Toxicology, 2023)

Seismic performance and analysis of resilient high-strength SRAC walls - Man Zhang; Jianwei Zhang; Yuping Sun; Xinyi Tao (Engineering Structures, 2023)

Near-infrared electrochemiluminescence of defect-rich molybdenum disulfide quantum dots for sensitive bioanalysis - Mingyue Chen; Yuzhu Sun; Hongfei Ji; Man Jiang; Wendong Liu; Mingzheng Shao; Zhe Hao; Hongyan Zhang; Xiyan Li; Yanfeng Dang; Ruizhong Zhang; Libing Zhang (Chemical Engineering Journal, 2023)

A new method for detecting karst and groundwater by 3D seismic wave: case study of the karst tunnel in Zhangjihuai Railway, China - Guochong Lou; Yang Song; Lingcong Man; Zhitao Sun (Bulletin of Engineering Geology and the Environment, 2023)

Versatile wheat gluten: functional properties and application in the food-related industry - Mengli Zhang; Ruobing Jia; Meng Ma; Tianbao Yang; Qingjie Sun; Man Li (Critical Reviews in Food Science and Nutrition, 2023)

Assessment of effectiveness in stabilization/solidification of arsenic-contaminated soil: long-term leaching test and geophysical measurement - Sun-Jae Lee; Man ho Han; Yong-Tae Ahn; Byong-Hun Jeon; Jaeyoung Choi (Environmental Science and Pollution Research, 2023)

Three new triterpenoid glycosides from Aronia melanocarpa (Michx.) Elliott - Ting-Ting Guo; Man-Li Zhang; Zhao-Cui Sun; Li-Mei Zhang; Xu-Dong Xu; Bi-Huang Hu (Natural Product Research, 2023)

One-shot domain adaptive real-time 3D obstacle detection in farmland based on semantic-geometry-intensity fusion strategy - Tianhai Wang; Ning Wang; Jianxing Xiao; Yanlong Miao; Yifan Sun; Han Li; Man Zhang (Computers and Electronics in Agriculture, 2023)

Ambient cold exposure amplifies the effect of ambient PM1 on blood pressure and hypertensive disorders of pregnancy among Chinese pregnant women: A nationwide cohort study - Yongqing Sun; Man Zhang; Wenjing Wu; Ruixia Liu; Yue Zhang; Shaofei Su; Enjie Zhang; Lijuan Sun; Wentao Yue; Qingqing Wu; Gongbo Chen; Wangjian Zhang; et al. (Science of The Total Environment, 2023)

Tuning MXene electrical conductivity towards multifunctionality - Lu Jia; Suqin Zhou; Abbas Ahmed; Zhichao Yang; Shuqiang Liu; Hua Wang; Fu Li; Man Zhang; Yujing Zhang; Luyi Sun (Chemical Engineering Journal, 2023)

Lithiophilic Sn layer via pre-electroplating to realize the uniform stripping/plating for dendrite free Li metal anodes - Wenlong Liu; Jianzong Man; Yiwen Guo; Yehong Du; Kun Liu; Haibang Zhang; Xiaodong Sun; Ning Zhang; Shize Fu; Juncai Sun (Chemical Engineering Journal, 2023)

Establishment and characterization of a liver cell line from silver pomfret ( Pampus argenteus ) for studying fish health - Huan Jiang; Youyi Zhang; Xiangbing Wang; Guanlin Wang; Jiajie Zhu; Jiachu Sun; Man Zhang; Yaya Li; Shanliang Xu; Jiabao Hu; Yajun Wang (Journal of Fish Diseases, 2023)
Fish cell lines have become a useful tool to study in resource conservation, genetic breeding, diseases control, and environmental pollutants detection. The silver pomfret ( Pampus argenteus ) is a high‐valued marine fish species in aquaculture, which is seriously threatened by various fish diseases. In this study, a new cell line derived from P. argenteus liver (PaL) was established and characterized. PaL cells mainly consisted of fibroblast‐like morphology and multiplied well in Leibovitz's L‐15 medium supplemented with 15% foetal bovine serum and 3 ng/mL basic fibroblast growth factor at 22°C. Amplification of the Cyt b gene confirmed that the origin of PaL cells as P. argenteus . Chromosome analysis revealed that PaL cells had a diploid Karyotyp. The PaL cells were efficiently transfected with pEGFP‐N3 plasmids, indicating its potential application in foreign gene manipulation studies. The PaL cells were found to be susceptible to red sea bream iridovirus (RSIV) and the expression of immune‐related gene ( TLR5 ) and apoptosis‐related genes ( Bax , Cyt c3 , CASP9 ) were upregulated. Furthermore, lipopolysaccharide and palmitic acid (PA) treatments decreased cell viability and up‐regulated the expression of inflammation related genes ( IL‐8 , IL‐1β ). Meanwhile, PA incubation induced cell apoptosis by Bcl‐2‐regulated caspase activation. In conclusion, the newly established PaL cell line will be an appropriate in vitro tool for viral propagation and immune response.

Using association mapping and local interval haplotype association analysis to improve the cotton drought stress response - Wenju Gao; Qin Chen; Jincheng Fu; Hui Jiang; Fenglei Sun; Shiwei Geng; Yuxiang Wang; Jieyin Zhao; Yuting Xie; Man Zhou; Yanying Qu; Quanjia Chen (Plant Science, 2023)

Short-term exposure to ozone and ECG abnormalities in China: A nationwide longitudinal study - Zhaoyang Pan; Xueyan Han; Man Cao; Jian Guo; Dengmin Huang; Wei Sun; Jiarun Mi; Yuanli Liu; Tao Xue; Tianjia Guan (Journal of Hazardous Materials, 2023)

Tree roots exert greater impacts on phosphorus fractions than aboveground litter in mineral soils under a Pinus sylvestris var. mongolica plantation - Xiang Zhang; Qiong Zhao; Li-Man Wei; Qing-Ye Sun; De-Hui Zeng (Forest Ecology and Management, 2023)

Thienoacene-fused fluorophores for highly efficient deep red/near-infrared OLEDs - Li Zhu; Yixia Liu; Xiaofei Wang; Kai Zhang; Jing-Wen Tai; Yan-Qiu Sun; Chuan-Kui Wang; Lei Ding; Man-Keung Fung; Jian Fan (Chemical Engineering Journal, 2023)

Stability control measures for roof cutting and NPR supporting of mining roadways in fault areas of kilometre-deep coal mine - Xiao-ming Sun; Jian Wang; Yong Zhang; Wen-chao Zhao; Zhi-biao Guo; Man-chao He; Feng Chen; Cheng-yu Miao (Journal of Mountain Science, 2023)

Density Functional Theory Study of Marine Polybrominated Diphenyl Ethers in Anaerobic Degradation - Xiang Xu; Miaomiao Man; Qinxing Sun; Qingzhi Liu; Kechen Wu; Dengfeng Yang (Journal of Ocean University of China, 2023)

Correction to: Silica nanoparticle exposure inducing granulosa cell apoptosis and follicular atresia in female Balb/c mice - Jianhui Liu; Man Yang; Li Jing; Lihua Ren; Jialiu Wei; Jin Zhang; Feng Zhang; Junchao Duan; Xianqing Zhou; Zhiwei Sun (Environmental Science and Pollution Research, 2023)

Study on the ditching of space capsules using the smoothed particle hydrodynamics method - Xin-Yang Ju; Peng-Nan Sun; Yan-Ming Shen; Jian-Qiang Chen; A-Man Zhang (Ocean Engineering, 2023)

Changes in gut microbiota structure and function in gout patients - Feiyan Zhao; Zhixin Zhao; Dafu Man; Zhihong Sun; Ning Tie; Hongbin Li; Heping Zhang (Food Bioscience, 2023)

Crop productivity and soil inorganic carbon change mediated by enhanced rock weathering in farmland: A comparative field analysis of multi-agroclimatic regions in central China - Fuxing Guo; Yanping Wang; Haoyong Zhu; Chuangye Zhang; Haowei Sun; Zhuling Fang; Jing Yang; Linsen Zhang; Yan Mu; Yu Bon Man; Fuyong Wu (Agricultural Systems, 2023)

Short-chain fatty acids (SCFAs) as potential resuscitation factors that promote the isolation and culture of uncultured bacteria in marine sediments - Chun-Shui Sun; Liu-Yan Zhou; Qi-Yun Liang; Xiao-Man Wang; Yi-Xuan Lei; Zhen-Xing Xu; Feng-Qing Wang; Guan-Jun Chen; Zong-Jun Du; Da-Shuai Mu (Marine Life Science & Technology, 2023)
Many marine bacteria are difficult to culture because they are dormant, rare or found in low-abundances. Enrichment culturing has been widely tested as an important strategy to isolate rare or dormant microbes. However, many more mechanisms remain uncertain. Here, based on 16S rRNA gene high-throughput sequencing and metabolomics technology, it was found that the short-chain fatty acids (SCFAs) in metabolites were significantly correlated with uncultured bacterial groups during enrichment cultures. A pure culture analysis showed that the addition of SCFAs to media also resulted in high efficiency for the isolation of uncultured strains from marine sediments. As a result, 238 strains belonging to 10 phyla, 26 families and 82 species were successfully isolated. Some uncultured rare taxa within Chlorobi and Kiritimatiellaeota were successfully cultured . Amongst the newly isolated uncultured microbes, most genomes, e.g. bacteria, possess SCFA oxidative degradation genes, and these features might aid these microbes in better adapting to the culture media. A further resuscitation analysis of a viable but non-culturable (VBNC) Marinilabiliales strain verified that the addition of SCFAs could break the dormancy of Marinilabiliales in 5 days, and the growth curve test showed that the SCFAs could shorten the lag phase and increase the growth rate. Overall, this study provides new insights into SCFAs, which were first studied as resuscitation factors in uncultured marine bacteria. Thus, this study can help improve the utilisation and excavation of marine microbial resources, especially for the most-wanted or key players.

N6-methyladenosine upregulates ribosome biogenesis in environmental carcinogenesis - Tianhe Zhao; Donglei Sun; Keyan Long; Bernardo Lemos; Qian Zhang; Jin Man; Manyu Zhao; Zunzhen Zhang (Science of The Total Environment, 2023)

Fermented mixed feed regulates intestinal microbial community and metabolism and alters pork flavor and umami - Shiqi Liu; Yuang Tu; Jiabao Sun; Peiran Cai; Yanbing Zhou; Yuqin Huang; Shu Zhang; Wentao Chen; Liyi Wang; Man Du; Wenjing You; Tenghao Wang; et al. (Meat Science, 2023)

Failure mechanism and control countermeasures of surrounding rock at deep large section chamber intersection in the Wanfu Coal Mine - Xiao-ming Sun; Zhen-min Qi; Yong Zhang; Cheng-yu Miao; Cheng-wei Zhao; Man-chao He (Journal of Mountain Science, 2023)

Effects of different photoperiods on growth and ovarian development and maturation of silver pomfret Pampus argenteus - Xiangbing Wang; Yaya Li; Jiabao Hu; Youyi Zhang; Man Zhang; Guanlin Wang; Huan Jiang; Jiachu Sun; Chunyang Guo; Shanliang Xu; Yang Yang; Yajun Wang; et al. (Journal of Fish Biology, 2023)
Photoperiod has a great influence on the growth and ovarian development and maturation of fishes. To analyse the effects of photoperiod on growth and ovarian development of an important marine economic fish, silver pomfret Pampus argenteus , short photoperiod group (L:D = 8:16), control group (L:D = 12:12) and long photoperiod group (L:D = 18:6) were set up for 60 days. The growth performance, ovarian development, changes in hormones and key enzyme activities in the hypothalamic–pituitary−gonadal (HPG) axis and expressions of key regulatory genes in the HPG axis were studied under different photoperiod conditions. The results showed that the final weight gain, body weight index, specific growth rate for weight, specific growth rate for length and average daily growth were the highest in the long photoperiod group, and the feed conversion rate was the lowest. Under long photoperiod condition, gonado‐somatic index and hepato‐somatic index were higher, ovarian maturity was better and expressions of HPG axis−related regulatory genes foxl2a , foxl2b , cyp19a1a , cyp19a1b , kiss , gpr54‐2 , gnrh2 , fsh and lh were higher. When compared with the other two groups, in the long photoperiod group, the change trend of estradiol (E2) was consistent with those of luteinizing hormone, melatonin (MT) and kisspeptin, and the levels were higher on the 20th and 50th days. These results indicate that prolongation of the photoperiod can improve the growth performance of P. argenteus and promote ovary development and maturation. The authors speculate that photoperiod may regulate the ovarian activity of P. argenteus through MT and kisspeptin/gpr54 signalling pathways. The results show that photoperiod can regulate the ovarian development of P. argenteus , which would help in breaking the seasonal restrictions of animals and regulating an animal's reproductive cycle.

Peptide profiles and allergy-reactivity of extensive hydrolysates of milk protein - Qiang Cui; Zhiqing Zhang; Meiliang Li; Man Zhou; Xiaomeng Sun (Food Chemistry, 2023)

Potential impact of ambient temperature on maternal blood pressure and hypertensive disorders of pregnancy: A nationwide multicenter study based on the China birth cohort - Yongqing Sun; Man Zhang; Shirui Chen; Wangjian Zhang; Yue Zhang; Shaofei Su; Enjie Zhang; Lijuan Sun; Kai Yang; Jingjing Wang; Wentao Yue; Qingqing Wu; et al. (Environmental Research, 2023)

Intermolecular interactions and gel properties of composite agglomerative networks based on oppositely charged polymers: Effects of pH and ionic strength - Xinyue Yan; Yijia Jia; Hui Man; Lu Liu; Shiyan Sun; Baokun Qi; Yang Li (Food Hydrocolloids, 2023)

Porous carbon nanofibers supported Zn@MnO sorbents with high dispersion and loading content for hot coal gas desulfurization - Yu Feng; Man Zhang; Yangjie Sun; Chunyan Cao; Jiancheng Wang; Mingzheng Ge; Weilong Cai; Jie Mi; Yuekun Lai (Chemical Engineering Journal, 2023)

Long-term waterborne Cu2+ exposure affects collagen metabolism in fish - Youyi Zhang; Feirong Yuan; Kaiheng Yan; Man Zhang; Yaya Li; Guanlin Wang; Huan Jiang; Xiangbin Wang; Jiajie Zhu; Jiachu Sun; Shanliang Xu; Jiabao Hu; et al. (Aquatic Toxicology, 2023)

Greenhouse gas emissions from wastewater treatment plants in China: Historical emissions and future mitigation potentials - Mengjie Yang; Man Peng; Dong Wu; Haoyuan Feng; Yixian Wang; Yongpeng Lv; Fengyun Sun; Sanjib Sharma; Yue Che; Kai Yang (Resources, Conservation and Recycling, 2023)

N6-methyladenosine plays a dual role in arsenic carcinogenesis by temporal-specific control of core target AKT1 - Tianhe Zhao; Donglei Sun; Wenxiao Xiong; Jin Man; Qian Zhang; Manyu Zhao; Zunzhen Zhang (Journal of Hazardous Materials, 2023)

Differential characteristics of carbon emission efficiency and coordinated emission reduction pathways under different stages of economic development: Evidence from the Yangtze River Delta, China - Chonggang Liu; Wei Sun; Pingxing Li; Luocheng Zhang; Man Li (Journal of Environmental Management, 2023)

Complete mitochondrial genome of the forensically important carrion beetle, Necrodes nigricornis (Coleoptera: Silphidae) - Man Il Kim; Jeong Sun Park; Chong Min Choung; Min Jee Kim; Iksoo Kim (Journal of Asia-Pacific Entomology, 2023)

Highly efficient generation of blastocyst-like structures from spliceosomes-repressed mouse totipotent blastomere-like cells - Pengfei Zhang; Xuzhao Zhai; Boyan Huang; Shu Sun; WenJing Wang; Man Zhang (Science China Life Sciences, 2023)

Fabrication of In–S-co-doped two-dimensional BiOCl coupling with surface hydroxylation toward simultaneously efficient charge separation and redox capability for photocatalytic water remediation - Tingfang Xie; Shaodong Sun; Yu Guo; Yongguang Luo; Man Yang; Bian Yang; Jie Cui (Chemosphere, 2023)

Simultaneous sludge minimization and membrane fouling mitigation in membrane bioreactors by using a microaerobic - Settling pretreatment module - Yi Zuo; Yanjun Shao; Lihua Wang; Yiyue Sun; Ying An; Lu-Man Jiang; Nan Yu; Rujie Hao; Chuanting Zhou; Jun Tao; Zhen Zhou (Journal of Environmental Management, 2023)

Tracking the driving forces for the unfolding and folding of kidney bean protein isolates: Revealing mechanisms of dynamic changes in structure and function - Xinyue Yan; Yijia Jia; Hui Man; Shiyan Sun; Yuyang Huang; Baokun Qi; Yang Li (Food Chemistry, 2023)

Cholesterol homeostasis regulated by ABCA1 is critical for retinal ganglion cell survival - Jialiang Yang; Yuhong Chen; Tongdan Zou; Bai Xue; Fang Yang; Xiangzhou Wang; Yibo Huo; Boyun Yan; Yuxia Xu; Shiyu He; Yi Yin; Jing Wang; et al. (Science China Life Sciences, 2023)

Oligosaccharide analysis of the backbone structure of the characteristic polysaccharide of Dendrobium officinale - Tin-Long Wong; Li-Feng Li; Ji-Xia Zhang; Quan-Wei Zhang; Xue-Ting Zhang; Li-Shuang Zhou; Hau-Yee Fung; Lei Feng; Hui-Yuan Cheng; Chu-Ying Huo; Man Liu; Wan-Rong Bao; et al. (Food Hydrocolloids, 2023)

Best practices for correlating electrical conductivity with broadband EMI shielding in binary filler-based conducting polymer composites - Junpyo Hong; Jisung Kwon; Dohyun Im; Jeonggil Ko; Chae Yun Nam; Hyeong Gyu Yang; Sun Ho Shin; Soon Man Hong; Seung Sang Hwang; Ho Gyu Yoon; Albert S. Lee (Chemical Engineering Journal, 2023)

Aaptamine derivatives with CDK2 inhibitory activities from the South China Sea sponge Aaptos suberitoides - Qian-Qian He; Yu-Qing Man; Kun-Lai Sun; Li-Juan Yang; Yan Wu; Jing Du; Wei-Wei Chen; Juan-Juan Dai; Na Ni; Shuang Miao; Kai-Kai Gong (Natural Product Research, 2022)

Distribution characteristics and risk assessment of heavy metals in seawater, sediment and shellfish in the inner and outer Daya Bay, Guangdong - Xiaodong Yu; Lianpeng Sun; Xinzhe Zhu; Guojian Bian; Wen Zhou; Qian Cao; Man Hong (Frontiers in Marine Science, 2022)
We investigated the distribution, sources, and ecological risks of heavy metals (As, Hg, Zn, Cd, Pb, Cu, and Cr) in seawater, sediments, and shellfish in the inner and outer waters of Daya Bay. 42 seawater quality survey sites, 21 sediment survey sites and 21 biological survey sites were set up in the study area. Our results showed that Daya Bay’s seawater is both clean and has a high Cu exceedance factor. The sediment heavy metal potential ecological hazard indices are all less than 40, which indicates a minimal degree of risk. E RI in the bay (mean value of E RI is 25.43) and that outside the bay (mean value of 23.56) is lower than 150, so the potential impact on the ecosystem is relatively low. In the Bay, Hg and Zn are primarily from fossil fuel and coal combustion, which enter the ocean via dry and wet deposition or surface runoff. Outside the Bay, Cr, Cu, Zn and Pb are derived the combustion waste gases of ships that enter the ocean via atmospheric deposition. Concerningly, arsenic and lead level in shellfish organisms appear to be above the standard values.However, because THQ and TTHQ are less than 1, there is no potential risk to human health. The weekly assessed intakes (EWIs) of Hg, AS, Pb, and Cd in shellfish inside and outside Daya Bay were 0.093 (0.058 outside the Bay), 0.594 (0.534), 1.115 (1.489), and 0.201 (0.190), respectively, all of these values were lower than the provisional PTWI for humans established by WHO. This indicates that the probability of carcinogenic risk to the population from heavy metals in shellfish are all below unacceptable levels.

GITRL impairs the immunosuppressive function of MDSCs via PTEN-mediated signaling pathway in experimental Sjögren syndrome - Jie Tian; Beibei Zhang; Qingfang Yuan; Xueqing Sun; Na Peng; Bo Zhu; Chang Liu; Xiaoran Wang; Man Han; Meng Cao; Fan Xiao; Shengjun Wang; et al. (Inflammation Research, 2022)

Recent advances in biotechnological production of polyunsaturated fatty acids by Yarrowia lipolytica - Yu-Lei Jia; Ling-Ru Wang; Zi-Xu Zhang; Yang Gu; Xiao-Man Sun (Critical Reviews in Food Science and Nutrition, 2022)

Dissolved oxygen gradient on three dimensionally printed microfluidic platform for studying its effect on fish at three levels: cell, embryo, and larva - Ping Liu; Longwen Fu; Bowei Li; Mingsan Man; Yunxia Ji; Qi Kang; Xiyan Sun; Dazhong Shen; Lingxin Chen (Environmental Science and Pollution Research, 2022)

Expression and cellular localization of insulin-like growth factor 3 in gonads of the seasonal breeding teleost silver pomfret (Pampus argenteus) - Yaya Li; Yang Yang; Youyi Zhang; Jiabao Hu; Man Zhang; Jiachu Sun; Xinyue Tian; Yuxuan Jin; Dingyuan Zhang; Yajun Wang; Shanliang Xu; Xiaojun Yan (Fish Physiology and Biochemistry, 2022)

Extended State Observer-Based Parameter Identification of Response Model for Autonomous Vessels - Man Zhu; Wuqiang Sun; Yuanqiao Wen; Liang Huang (Journal of Marine Science and Engineering, 2022)
Identification of parameters involved in the linear response model with high precision is a highly cost-effective, as well as a challenging task, in developing a suitable model for the verification and validation (V+V) of some key techniques for autonomous vessels in the virtual testbed, e.g., guidance, navigation, and control (GNC). In order to deal with this identification problem, a novel identification framework is proposed in this paper by introducing the extended state observer (ESO), and the well-evaluated robust weighted least square support vector regression algorithm (RW-LSSVR). A second-order linear response model is investigated in this study due to its wide use in controller designs. Considering the highly possible situation that only limited states could be measured directly, the required but immeasurable states in identifying parameters contained in the response model are approximately estimated by the ESO. Theoretical analysis of the stability is given to show and improve the applicability of the ESO. Simulation studies based on linear response models with predefined parameter values of a cargo vessel and a patrol vessel maneuvering in an open water area are carried out, respectively. Results show that the proposed approach not only estimates immeasurable states with high accuracy but also ensures good performance on the parameter identification of the response model with very close values to the nominal ones. The proven identified approach is economic because it only requires limited kinds of low-cost sensors.

Dissolved Pb Concentrations and Stable Pb Isotope Ratios in the Ulleung Basin, East/Japan Sea - Seonghu Choi; Man-Sik Choi; Dongjin Joe; Sojung Park; Jinwoo Kim; Kongtae Ra; Intae Kim; Kyung-Tae Kim; Kyoung-Seok Lee; Jean-Sun Lim (Ocean Science Journal, 2022)

Asymmetric Contribution of Blastomere Lineages of First Division of the Zygote to Entire Human Body Using Post-Zygotic Variants - Seong Gyu Kwon; Geon Hue Bae; June Hyug Choi; Nanda Maya Mali; Mee Sook Jun; Dong Sun Kim; Man-Hoon Han; Seongyeol Park; Young Seok Ju; Seock Hwan Choi; Ji Won Oh (Tissue Engineering and Regenerative Medicine, 2022)

Dogs lacking Apolipoprotein E show advanced atherosclerosis leading to apparent clinical complications - Hui Zhao; Jianping Zhao; Di Wu; Zhaolin Sun; Yang Hua; Min Zheng; Yumei Liu; Qi Yang; Xiahe Huang; Yuan Li; Yueshan Piao; Yingchun Wang; et al. (Science China Life Sciences, 2022)

A novel mutant PIK3R1EY451delinsD breast cancer patient resistant to HER2-targeted therapy treated with everolimus: a case report - Kainan Wang; Ye Hu; Lingzhi Xu; Shanshan Zhao; Chen Song; Siwen Sun; Xuelu Li; Man Li (Molecular Biology Reports, 2022)

High-throughput “read-on-ski” automated imaging and label-free detection system for toxicity screening of compounds using personalised human kidney organoids - Qizheng Wang; Jun Lu; Ke Fan; Yiwei Xu; Yucui Xiong; Zhiyong Sun; Man Zhai; Zhizhong Zhang; Sheng Zhang; Yan Song; Jianzhong Luo; Mingliang You; et al. (Journal of Zhejiang University-SCIENCE B, 2022)

Transcriptomics and transmission ultrastructural examination reveals the nephrotoxicity of cadmium in laying hens - Man Zhao; Wenbo He; Can Tao; Beiyu Zhang; Shuai Wang; Zhangjian Sun; Zhifeng Xiong; Niya Zhang (Environmental Science and Pollution Research, 2022)

Functional connectivity dynamics as a function of the fluctuation of tension during film watching - Yadi Sun; Junji Ma; Miner Huang; Yangyang Yi; Yiheng Wang; Yue Gu; Ying Lin; Liman Man Wai Li; Zhengjia Dai (Brain Imaging and Behavior, 2022)

3D Seismic Stability Analysis of Bench Slope with Pile Reinforcement - Sheng-yu Yang; Zhen Wang; Jia-man Wang; Ming-wei Gong; Jian-fei Li; Zhi-bin Sun (Geotechnical and Geological Engineering, 2022)

Predictive factors, preventive implications, and personalized surgical strategies for bone metastasis from lung cancer: population-based approach with a comprehensive cancer center-based study - Xianglin Hu; Wending Huang; Zhengwang Sun; Hui Ye; Kwong Man; Qifeng Wang; Yangbai Sun; Wangjun Yan (EPMA Journal, 2022)

Dysfunction of FadA‐cAMP signalling decreases Aspergillus flavus resistance to antimicrobial natural preservative Perillaldehyde and AFB1 biosynthesis - Kunlong Yang; Qingru Geng; Yue Luo; Rui Xie; Tongzheng Sun; Zhen Wang; Ling Qin; Wei Zhao; Man Liu; Yongxin Li; Jun Tian (Environmental Microbiology, 2022)
Summary Aspergillus flavus is an opportunistic fungal pathogen that colonizes agriculture crops with aflatoxin contamination. We found that Perillaldehyde (PAE) effectively inhibited A . flavus viability and aflatoxin production by inducing excess reactive oxygen species (ROS). Transcriptome analysis indicated that the Gα protein FadA was significantly induced by PAE. Functional characterization of FadA showed it is important for asexual development and aflatoxin biosynthesis by regulation of cAMP‐PKA signalling. The Δ fadA mutant was more sensitive to PAE, while Δ pdeL and Δ pdeH mutants can tolerate excess PAE compared to wild‐type A . flavus . Further RNA‐sequence analysis showed that fadA was important for expression of genes involved in oxidation–reduction and cellular metabolism. The flow cytometry and fluorescence microscopy demonstrated that Δ fadA accumulated more concentration of ROS in cells, and the transcriptome data indicated that genes involved in ROS scavenging were downregulated in Δ fadA mutant. We further found that FadA participated in regulating response to extracellular environmental stresses by increasing phosphorylation levels of MAPK Kinase Slt2 and Hog1. Overall, our results indicated that FadA signalling engages in mycotoxin production and A . flavus resistance to antimicrobial PAE, which provide valuable information for controlling this fungus and AF biosynthesis in pre‐ and postharvest of agricultural crops.

Sex-specific mediation of placental inflammatory biomarkers in the effects of prenatal phthalate coexposure on preschooler cognitive development - Hui Gao; Juan Tong; Bei-bei Zhu; Meng-long Geng; Hong Gan; Li Sun; Xiao-yan Wu; Kun Huang; Hui Cao; Wen-wen Liu; Shu-man Tao; Peng Ding; et al. (Environmental Science and Pollution Research, 2022)

Genetic diversity and structure of Oncomelania hupensis hupensis in two eco-epidemiological settings as revealed by the mitochondrial COX1 gene sequences - Jie-Ying Zhang; Man-Man Gu; Qiu-Fu Yu; Meng-Tao Sun; Hui-Ying Zou; Zhi-Jun Zhou; Da-Bing Lu (Molecular Biology Reports, 2022)

Neonatal Anesthesia by Ketamine in Neonatal Rats Inhibits the Proliferation and Differentiation of Hippocampal Neural Stem Cells and Decreases Neurocognitive Function in Adulthood via Inhibition of the Notch1 Signaling Pathway - He Huang; Chao Zhao; Qian Hu; Qiang Liu; Yi-Man Sun; Chen Chen; Hui Huang; Cheng-Hua Zhou; Yu-Qing Wu (Molecular Neurobiology, 2021)

TUG1 knockdown suppresses cardiac fibrosis after myocardial infarction - Qingsong Sun; Man Luo; Zhiwei Gao; Xiang Han; Zhuan Yan; Shouxiang Xie; Hongmei Zhao; Hong Sun (Mammalian Genome, 2021)

Immune response of silver pomfret ( Pampus argenteus ) to Amyloodinium ocellatum infection - Youyi Zhang; Jiabao Hu; Yaya Li; Man Zhang; Kimran Jean Jacques; Weiwei Gu; Yibo Sun; Jiachu Sun; Yang Yang; Shanliang Xu; Yajun Wang; Xiaojun Yan (Journal of Fish Diseases, 2021)
Amyloodinium ocellatum (AO) infection in silver pomfret ( Pampus argenteus ) causes extensive mortality. Insufficient information exists on the molecular immune response of silver pomfret to AO infestation, so herein we simulated the process of silver pomfret being infected by AO. Translucent trophosomes were observed on the gills of AO‐infected fish. Transcriptome profiling was performed to investigate the effects of AO infection on the gill, kidney complex and spleen. Overall, 404,412,298 clean reads were obtained, assembling into 96,341 unigenes, which were annotated against public databases. In total, 2730 differentially expressed genes were detected, and few energy‐ and immune‐related genes were further assessed using RT‐qPCR. Moreover, activities of three immune‐related (SOD, AKP and ACP) and three energy‐related (PKM, LDH and GCK) enzymes were determined. AO infection activated the immune system and increased interleukin‐1 beta and immunoglobulin M heavy chain levels. Besides, the PPAR signalling pathway was highly enriched, which played a role in improving immunity and maintaining homeostasis. AO infection also caused dyspnoea, leading to extensive lactic acid accumulation, potentially contributing towards a strong immune response in the host. Our data improved our understanding regarding the immune response mechanisms through which fish coped with parasitic infections and may help prevent high fish mortality in aquaculture.

Correction to: Exogenous toluene gas removal improvement in recombinant rabbit cytochrome P450 2E1 (CYP2E1)‑transgenic Ardisia pusilla DC - Nan‑Sun Kim; Ju Young Shin; Young Ah Lee; Kwang Jin Kim; Jeong Ho Kim; Hye Ryun An; Pue Hee Park; Pil Man Park; Su Young Lee (Horticulture, Environment, and Biotechnology, 2021)

Exogenous toluene gas removal improvement in recombinant rabbit cytochrome P450 2E1 (CYP2E1)-transgenic Ardisia pusilla DC - Nan-Sun Kim; Ju Young Shin; Young Ah Lee; Kwang Jin Kim; Jeong Ho Kim; Hye Ryun An; Pue Hee Park; Pil Man Park; Su Young Lee (Horticulture, Environment, and Biotechnology, 2021)

Deep learning model for prediction of extended-spectrum beta-lactamase (ESBL) production in community-onset Enterobacteriaceae bacteraemia from a high ESBL prevalence multi-centre cohort - Alfred Lok Hang Lee; Curtis Chun Kit To; Angus Lang Sun Lee; Ronald Cheong Kin Chan; Janus Siu Him Wong; Chun Wai Wong; Viola Chi Ying Chow; Raymond Wai Man Lai (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Variegated transnational partnerships: Multi-scalar actor networks in China’s overseas industrial parks - Tao Song; Man Sun; Yutian Liang; Soavapa Ngampramuan; Yeerken Wuzhati; Keyang Zhou (Journal of Geographical Sciences, 2021)

Poor outcomes of early recurrent post-transplant bloodstream infection in living-donor liver transplant recipients - Si-Ho Kim; Seok Jun Mun; Jae-Hoon Ko; Kyungmin Huh; Sun Young Cho; Cheol-In Kang; Doo Ryeon Chung; Gyu-Seong Choi; Jong Man Kim; Jae-Won Joh; Kyong Ran Peck (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Effects of Exposure to Lead and Cadmium on Health of Inhabitants of Abandoned Metal Mine Area in Korea - Joo-Young Moon; Sang-Yong Eom; Jeong-Wook Seo; Jung-Eum Lee; Byung-Sun Choi; Heon Kim; Young-Seoub Hong; Jun Young Chang; Man-Joong Jeon; Won-Ju Park; Joon Sakong; Jung-Duck Park (Archives of Environmental Contamination and Toxicology, 2021)

High‐resolution distribution pattern of surface water nitrous oxide along a cruise track from the Okhotsk Sea to the western Arctic Ocean - Liyang Zhan; Jiexia Zhang; Zhangxian Ouyang; Ruibo Lei; Suqing Xu; Di Qi; Zhongyong Gao; Heng Sun; Yuhong Li; Man Wu; Jian Liu; Liqi Chen (Limnology and Oceanography, 2021)
Nitrous oxide in the surface water was measured using an automatic underway system, along with measurements of surface water pCO 2 , dissolved oxygen, salinity, temperature, and sea ice coverage, along a cruise track through the Bering Sea and Chukchi Sea to the Canadian Basin during the 7 th Chinese National Arctic Research Expedition. The results show that, overall, the regions along the cruise track are net sources of N 2 O to the atmosphere. Several N 2 O oversaturation maxima were observed along the cruise track, with an absolute maximum of approximately 60%. According to the hydrographic setting and the distribution patterns of pCO 2 , dissolved oxygen, and sea ice coverage in the study area, it was concluded that the N 2 O oversaturation maxima may result from hydrographic processes, such as mixing of different water masses, upwelling or convection, and possible production beneath the sea ice. Additionally, the lowest value of approximately 90% may result from dilution related to the melting of sea ice. An evaluation of the air–sea flux along the cruise track shows that the continental shelf and upwelling region are N 2 O sources, whereas the study area in the open Arctic Ocean does not show obvious source or sink characteristics.

Footbinding and non-footbinding Han Chinese females in the Qing Dynasty (1644–1912 CE) Xifengbu cemetery: a skeletal and mortuary analysis - Xiaofan Sun; Xingyu Man; Xuezhu Liao; Jiyun Yang; Jun Cao; Hong Zhu; Quanchao Zhang; Qian Wang (Archaeological and Anthropological Sciences, 2021)

Effectiveness of Adding Antiplatelets to Oral Anticoagulants in Patients with Acute Ischemic Stroke with Atrial Fibrillation and Concomitant Large Artery Steno-Occlusion - Joon-Tae Kim; Ji Sung Lee; Beom Joon Kim; Jong-Moo Park; Kyusik Kang; Soo Joo Lee; Jae Guk Kim; Jae-Kwan Cha; Dae-Hyun Kim; Tai Hwan Park; Sang-Soon Park; Kyung Bok Lee; et al. (Translational Stroke Research, 2020)

A high-density genetic map and multiple environmental tests reveal novel quantitative trait loci and candidate genes for fibre quality and yield in cotton - Qishen Gu; Huifeng Ke; Zhengwen Liu; Xing Lv; Zhengwen Sun; Man Zhang; Liting Chen; Jun Yang; Yan Zhang; Liqiang Wu; Zhikun Li; Jinhua Wu; et al. (Theoretical and Applied Genetics, 2020)

Inversion of time-domain airborne EM data with IP effect based on Pearson correlation constraints - Man Kai-Feng; Yin Chang-Chun; Liu Yun-He; Ren Xiu-Yan; Sun Si-Yuan; Miao Jia-Jia; Xiong Bin (Applied Geophysics, 2020)

Enhanced detoxification of exogenous toluene gas in transgenic Ardisia pusilla expressing AtNDPK2 gene - Chang Ho Ahn; Nan-Sun Kim; Ju Young Shin; Young Ah Lee; Kwang Jin Kim; Jeong Ho Kim; Pil Man Park; Hye Ryun An; Yae-Jin Kim; Won Hee Kim; Su Young Lee (Horticulture, Environment, and Biotechnology, 2020)

Heroin Abuse and/or HIV Infection Dysregulate Plasma Exosomal miRNAs - Xu Wang; Li Sun; Yu Zhou; Qi-Jian Su; Jie-Liang Li; Li Ye; Man-Qing Liu; Wang Zhou; Wen-Zhe Ho (Journal of Neuroimmune Pharmacology, 2020)

Effects of dietary cadmium supplementation on production performance, cadmium residue in eggs, and hepatic damage in laying hens - Can Tao; Beiyu Zhang; Xiaotian Wei; Man Zhao; Zhangjian Sun; Shuai Wang; Jiwen Bi; Desheng Qi; Lvhui Sun; Niya Zhang (Environmental Science and Pollution Research, 2020)

Optimization of an mRNA vaccine assisted with cyclodextrin-polyethyleneimine conjugates - Lu Tan; Tao Zheng; Man Li; Xiaofang Zhong; Yao Tang; Ming Qin; Xun Sun (Drug Delivery and Translational Research, 2020)

Prevalence of RNF213 variants in symptomatic intracranial arterial stenosis/occlusion in China - Xunsha Sun; Man Luo; Jiaoxing Li; Rong Lai; Jing Lin; Yufang Wang; Xiaowei Xu; Shaoqing Wu; Wenli Sheng (Molecular Genetics and Genomics, 2020)

Dynamics of the gene regulatory networks of the inner and rosette leaves in Brassica rapa - Man-Sun Kim; Dongsan Kim; Seongmin Hong; Jeong-Rae Kim; Yong Pyo Lim (Horticulture, Environment, and Biotechnology, 2020)

APOD mission status and preliminary results - Geshi Tang; Xie Li; Jianfeng Cao; Shushi Liu; Guangming Chen; Haijun Man; Xiaomin Zhang; Sihan Shi; Ji Sun; Yongping Li; Andres Calabia (Science China Earth Sciences, 2020)

Hirsutella sinensis inhibits NLRP3 inflammasome activation to block aristolochic acid-induced renal tubular epithelial cell transdifferentiation - Min Yu; Yu-lin Man; Meng-hua Chen; Li-hua Wu; Yi Zhou; Xiao-ling Zhou; Na Chen; Rui Ma; Li-na Sun (Human Cell, 2020)

Triptolide suppresses pancreatic cancer cell proliferation by inhibiting hedgehog signaling pathway activity - Juanjuan Feng; Mingjin Rao; Man Wang; Lin Liang; Zhi Chen; Xiufeng Pang; Weiqiang Lu; Zhenliang Sun (Science China Life Sciences, 2019)

Molecular Screening of Behaviorally Active Compounds with CmedOBP14 from the Rice Leaf Folder Cnaphalocrocis medinalis - Shuang-Feng Sun; Fang-Fang Zeng; Shan-Cheng Yi; Man-Qun Wang (Journal of Chemical Ecology, 2019)

iTRAQ-based quantitative proteomic analysis of cotton (Gossypium hirsutum L.) leaves reveals pathways associated throughout the aging process - Liantao Liu; Anchang Li; Jing Chen; Man Wang; Yongjiang Zhang; Hongchun Sun; Xiaodan Wang; Cundong Li (Acta Physiologiae Plantarum, 2019)

Dynamic Effects of Ioversol on the Permeability of the Blood-Brain Barrier and the Expression of ZO-1/Occludin in Rats - Heying Wang; Tao Li; Lili Zhao; Man Sun; Yating Jian; Jiao Liu; Yiheng Zhang; Ye Li; Meijuan Dang; Guilian Zhang (Journal of Molecular Neuroscience, 2019)

Ghrelin Promotes Cortical Neurites Growth in Late Stage After Oxygen-Glucose Deprivation/Reperfusion Injury - Jing Liu; Man Chen; Ruirui Dong; Changwei Sun; Shuo Li; Shigong Zhu (Journal of Molecular Neuroscience, 2019)

Effect of silicon in Pyropia yezoensis under temperature and irradiance stresses through antioxidant gene expression - Bao Le; Mawra Nadeem; Seung-Hwan Yang; Jong-Am Shin; Man-Gu Kang; Gyuhwa Chung; Sangmi Sun (Journal of Applied Phycology, 2019)

Fecobionics: A Novel Bionics Device for Studying Defecation - Daming Sun; Zhiyong Huang; Zhuoli Zhuang; Zhiyao Ma; Lo Kar Man; Donghua Liao; Hans Gregersen (Annals of Biomedical Engineering, 2019)

Dioscin-6’-O-acetate impairs migration of lung cancer cells through attenuations of MMP-2 and MMP-9 via NF-κB suppression - Xuejiao Li; Jiachen Sun; Xia Li; Yujie Dai; Chengcheng Zhao; Shuli Man; Ying Wang; Wenyuan Gao (Medicinal Chemistry Research, 2019)

Sorption of Pb in chemical and particle-size fractions of soils with different physico-chemical properties - Hyun-Jung Park; Hyun-Jin Park; Hye In Yang; Se-In Park; Sang-Sun Lim; Jin-Hyeob Kwak; Goon-Taek Lee; Sang-Mo Lee; Man Park; Woo-Jung Choi (Journal of Soils and Sediments, 2019)

Description of Haemaphysalis (Alloceraea) Kolonini sp. nov., a new species in subgenus Alloceraea Schulze (Ixodidae: Haemaphysalis) in China - Chun-Hong Du; Yi Sun; Rong-Man Xu; ZongTi Shao (Acta Parasitologica, 2018)
Southeastern Asia has been postulated as probably the original sites of genus Haemaphysalis , where numerous structurally advanced haemaphysalids now occur. Because of its phylogenetic and biological interest, we report the discovery of a structurally primitive new species Haemaphysalis ( A .) kolonini belonging to subgenus Alloceraea from Baoshan and Weixi cities, Yunnan province, southwestern China. Both the morphological and phylogenic characteristics of the species support congruently to erect Hae . ( A .) kolonini as a new species. The male and female adults of Haemaphysalis ( A .) kolonini are respectively described and illustrated. Taxonomic discussion and keys to Alloceraea species in China are also provided to be able to distinguish species that are close morphologically.

Optimization of Hydrolysis Conditions for the Isolation of Angiotensin-I Converting Enzyme (ACE) Inhibitory Peptides from Rhopilema hispidum - Zhenliang Sun; Huanlong Qin; Duo Cao; Xuebing Yan; Hao Li; Linsheng Huang; Xiao Qu; Cheng Kong; Man Wang (Journal of Ocean University of China, 2018)

Plasma metabonomics investigation reveals involvement of fatty acid oxidation in hematotoxicity in Chinese benzene-exposed workers with low white blood cell count - Rongli Sun; Kai Xu; Qiaoyun Zhang; Xiaoyun Jiang; Zhaodi Man; Lihong Yin; Juan Zhang; Yuepu Pu (Environmental Science and Pollution Research, 2018)

Comprehensive analysis of CCCH zinc-finger-type transcription factors in the Brassica rapa genome - Jana Jeevan Rameneni; Vignesh Dhandapani; Parameswari Paul; Sangeeth Prasath Devaraj; Su Ryun Choi; So Young Yi; Man-Sun Kim; Seongmin Hong; Sang Heon Oh; Man-Ho Oh; Yong Pyo Lim (Horticulture, Environment, and Biotechnology, 2018)

Associations of HSP90AA2 gene polymorphisms with disease susceptibility, glucocorticoids efficacy and health-related quality of life in Chinese systemic lupus erythematosus patients - Man Zhang; Su-Su Li; Qiao-Mei Xie; Jian-Hua Xu; Xiu-Xiu Sun; Fa-Ming Pan; Sheng-Qian Xu; Sheng-Xiu Liu; Jin-Hui Tao; Shuang Liu; Jing Cai; Pei-Ling Chen; et al. (Genes & Genomics, 2018)

Enhanced growth rate and ulvan yield of Ulva pertusa using light-emitting diodes (LEDs) - Bao Le; Jong-Am Shin; Man-Gu Kang; Sangmi Sun; Seung Hwan Yang; Gyuhwa Chung (Aquaculture International, 2018)

Mechanical and Clinical Evaluation of a Shape Memory Alloy and Conventional Struts in a Flexible Scoliotic Brace - Wing-Yu Chan; Joanne Yip; Kit-Lun Yick; Sun-Pui Ng; Lu Lu; Kenneth Man-Chee Cheung; Kenny Yat-Hong Kwan; Jason Pui-Yin Cheung; Kelvin Wai-Kwok Yeung; Chi-Yung Tse (Annals of Biomedical Engineering, 2018)

SNAI1, an endothelial–mesenchymal transition transcription factor, promotes the early phase of ocular neovascularization - Jia-Xing Sun; Tian-Fang Chang; Man-Hong Li; Li-Juan Sun; Xian-Chun Yan; Zi-Yan Yang; Yuan Liu; Wen-Qin Xu; Yang Lv; Jing-Bo Su; Liang Liang; Hua Han; et al. (Angiogenesis, 2018)

Deletion of Type-2 Cannabinoid Receptor Induces Alzheimer’s Disease-Like Tau Pathology and Memory Impairment Through AMPK/GSK3β Pathway - Lin Wang; Bing-Jin Liu; Yun Cao; Wei-Qi Xu; Dong-Sheng Sun; Meng-Zhu Li; Fang-Xiao Shi; Man Li; Qing Tian; Jian-Zhi Wang; Xin-Wen Zhou (Molecular Neurobiology, 2018)

Competitive ability, stress tolerance and plant interactions along stress gradients - Man Qi; Tao Sun; SuFeng Xue; Wei Yang; DongDong Shao; Javier Martínez‐López (Ecology, 2018)
Exceptions to the generality of the stress‐gradient hypothesis ( SGH ) may be reconciled by considering species‐specific traits and stress tolerance strategies. Studies have tested stress tolerance and competitive ability in mediating interaction outcomes, but few have incorporated this to predict how species interactions shift between competition and facilitation along stress gradients. We used field surveys, salt tolerance and competition experiments to develop a predictive model interspecific interaction shifts across salinity stress gradients. Field survey and greenhouse tolerance tests revealed tradeoffs between stress tolerance and competitive ability. Modeling showed that along salinity gradients, (1) plant interactions shifted from competition to facilitation at high salinities within the physiological limits of salt‐intolerant plants, (2) facilitation collapsed when salinity stress exceeded the physiological tolerance of salt‐intolerant plants, and (3) neighbor removal experiments overestimate interspecific facilitation by including intraspecific effects. A community‐level field experiment, suggested that (1) species interactions are competitive in benign and, facilitative in harsh condition, but fuzzy under medium environmental stress due to niche differences of species and weak stress amelioration, and (2) the SGH works on strong but not weak stress gradients, so SGH confusion arises when it is applied across questionable stress gradients. Our study clarifies how species interactions vary along stress gradients. Moving forward, focusing on SGH applications rather than exceptions on weak or nonexistent gradients would be most productive.

Silica nanoparticle exposure inducing granulosa cell apoptosis and follicular atresia in female Balb/c mice - Jianhui Liu; Man Yang; Li Jing; Lihua Ren; Jialiu Wei; Jin Zhang; Feng Zhang; Junchao Duan; Xianqing Zhou; Zhiwei Sun (Environmental Science and Pollution Research, 2018)

Asymmetric reduction of ketopantolactone using a strictly (R)-stereoselective carbonyl reductase through efficient NADPH regeneration and the substrate constant-feeding strategy - Man Zhao; Liang Gao; Li Zhang; Yanbin Bai; Liang Chen; Meilan Yu; Feng Cheng; Jie Sun; Zhao Wang; Xiangxian Ying (Biotechnology Letters, 2017)

Histological analysis and identification of spermatogenesis-related genes in 2-, 6-, and 12-month-old sheep testes - Man Bai; Limin Sun; Jia Zhao; Lujie Xiang; Xiaoyin Cheng; Jiarong Li; Chao Jia; Huaizhi Jiang (The Science of Nature, 2017)

Purification and characterization of angiotensin I converting enzyme inhibition peptides from sandworm Sipunculus nudus - Xueping Sun; Man Wang; Buming Liu; Zhenliang Sun (Journal of Ocean University of China, 2017)

Synthesis and evaluation of novel urea and amide derivatives of 2-amino-4-phenylthiazole as potential antibacterial agents - Zhi-Hua Zhang; Yu Chen; Xin-Jia Yan; Yao Sun; Xiao-Man Yang; Xiao-Yu Cai; Song You (Medicinal Chemistry Research, 2017)

Microsatellite records for volume 9, issue 3 - Aiguo Yang; Biao Wu; Chao Shen; Guangming Zhang; Hanmiao Liu; Hongying Guo; Jiaman Li; Jinliang Liu; Liqing Zhou; Longbing Rao; Man Yang; Mengdi Li; et al. (Conservation Genetics Resources, 2017)

Occupational risk factors for nasopharyngeal carcinoma in Hong Kong Chinese: a case-referent study - Shao-Hua Xie; Ignatius Tak-sun Yu; Lap Ah Tse; Joseph Siu Kie Au; June Sze Man Lau (International Archives of Occupational and Environmental Health, 2017)

Landscape dynamics and driving forces of wetlands in the Tumen River Basin of China over the past 50 years - Xiao Jun Zheng; Peng Sun; Wei Hong Zhu; Zhen Xu; Jing Fu; Wei Dong Man; Hai Long Li; Jian Zhang; Lei Qin (Landscape and Ecological Engineering, 2017)

Therapeutic Hypothermia Enhances Cold-Inducible RNA-Binding Protein Expression and Inhibits Mitochondrial Apoptosis in a Rat Model of Cardiac Arrest - Lin Wu; He-liang Sun; Yu Gao; Kang-li Hui; Miao-miao Xu; Hao Zhong; Man-lin Duan (Molecular Neurobiology, 2017)

Furofuran lignan glucosides from the leaves of Vitex negundo var. cannabifolia - Yue-Ting Li; Man-Man Li; Jing Sun; Zhi-Xiang Zhu; Yue-Lin Song; Dao-Ran Pang; Jiao Zheng; Yun-Fang Zhao; Peng-Fei Tu; Jun Li (Natural Product Research, 2017)

Nuclear receptors regulate lipid metabolism and oxidative stress markers in chondrocytes - Anusha Ratneswaran; Margaret Man-Ger Sun; Holly Dupuis; Cynthia Sawyez; Nica Borradaile; Frank Beier (Journal of Molecular Medicine, 2017)

CYP1A1 based on metabolism of xenobiotics by cytochrome P450 regulates chicken male germ cell differentiation - Dong Li; Man Wang; Shaoze Cheng; Chen Zhang; Yilin Wang; Wenhui Zhang; Ruifeng Zhao; Changhua Sun; Yani Zhang; Bichun Li (In Vitro Cellular & Developmental Biology - Animal, 2017)

Effects of straw and biochar amendments on aggregate stability, soil organic carbon, and enzyme activities in the Loess Plateau, China - Man Zhang; Gong Cheng; Hao Feng; Benhua Sun; Ying Zhao; Haixin Chen; Jing Chen; Miles Dyck; Xudong Wang; Jianguo Zhang; Afeng Zhang (Environmental Science and Pollution Research, 2017)

Overexpression of a heading Chinese cabbage ICE1 gene confers freezing tolerance in transgenic rice - Dianjun Xiang; Yongshan Chai; Lili Man; Yuyou Sun; Taizhong Zhang; Caiqiang Wei; Zhong Xie; Hongliang Li; Weiwei Zhang; Dan Liu; Dujuan Cheng; Xiaodong Wang; et al. (Plant Cell, Tissue and Organ Culture (PCTOC), 2017)

Endosulfan inducing apoptosis and necroptosis through activation RIPK signaling pathway in human umbilical vascular endothelial cells - Lianshuang Zhang; Jialiu Wei; Lihua Ren; Jin Zhang; Man Yang; Li Jing; Ji Wang; Zhiwei Sun; Xianqing Zhou (Environmental Science and Pollution Research, 2017)

Plant receptor kinases bind and phosphorylate 14-3-3 proteins - Won Byoung Chae; Youn-Je Park; Kyung Sun Lee; Ill-Sup Nou; Man-Ho Oh (Genes & Genomics, 2016)

Endosulfan inhibiting the meiosis process via depressing expressions of regulatory factors and causing cell cycle arrest in spermatogenic cells - Fang-Zi Guo; Lian-Shuang Zhang; Jia-Liu Wei; Li-Hua Ren; Jin Zhang; Li Jing; Man Yang; Ji Wang; Zhi-Wei Sun; Xian-Qing Zhou (Environmental Science and Pollution Research, 2016)

Signaling Mechanism of Cannabinoid Receptor-2 Activation-Induced β-Endorphin Release - Fang Gao; Ling-Hong Zhang; Tang-Feng Su; Lin Li; Rui Zhou; Miao Peng; Cai-Hua Wu; Xiao-Cui Yuan; Ning Sun; Xian-Fang Meng; Bo Tian; Jing Shi; et al. (Molecular Neurobiology, 2016)

Simulating Dynamic Vegetation Changes in a Tidal Restriction Area with Relative Stress Tolerance Curves - Man Qi; Tao Sun; Min Zhan; SuFeng Xue (Wetlands, 2016)

Rapid expansion and auto-grafting efficiency of porcine full skin expanded by a skin bioreactor ex vivo - Man-Il Huh; Sun Hee An; Hwi-Gang Kim; Yun-Jeong Song; Eun-Chang Choi; Sang-Hyun An; Woo-Sung Choi; Jeung Soo Huh; Jeong Ok Lim (Tissue Engineering and Regenerative Medicine, 2016)

Heat stress impairs mice granulosa cell function by diminishing steroids production and inducing apoptosis - Man Luo; Lian Li; Cheng Xiao; Yu Sun; Gen-Lin Wang (Molecular and Cellular Biochemistry, 2016)

Impact of the North Atlantic Oscillation on the Dipole Oscillation of summer precipitation over the central and eastern Tibetan Plateau - Huancai Liu; Keqin Duan; Man Li; Peihong Shi; Junhua Yang; Xiao Zhang; Jianyong Sun (International Journal of Climatology, 2015)
An analysis of the spatiotemporal variability in summer precipitation during the period 1961–2010 is presented based on monthly precipitation datasets from 66 meteorological stations in the central and eastern Tibetan Plateau ( TP ). By applying empirical orthogonal function ( EOF ) analysis, a strong reversal is found in the variability of summer precipitation between the northeastern and the southeastern TP on the inter‐annual timescale; this reversal is defined as the Dipole Oscillation in summer precipitation over the TP . Our analysis shows that the North Atlantic Oscillation ( NAO ) greatly controls the Dipole Oscillation in TP summer precipitation by modifying the atmospheric circulation over and around the TP . With the increased stationary wave activity spreading eastward from the North Atlantic to the TP , a pronounced wave train pattern bridges the North Atlantic Ocean and the TP . During the positive phase of the NAO , warm moist air from the oceans around Asia is transported by the southeastern flank of the anticyclonic anomaly over East Asia to the northeastern TP . This northward‐moving warm moist air encounters cold air masses transported by the northwestern flank of the cyclonic anomaly over the northeastern TP . The confluence of the cold and warm air masses subsequently strengthens cumulus convective activities and ultimately results in excessive precipitation over the northeastern TP . Meanwhile, as a cyclonic anomaly sets up over northwestern India and Pakistan, water vapour condenses into precipitation over northwestern India and Pakistan, inhibiting Arabian Sea moisture inflows into the southeastern TP and northeastern India. As a result, a precipitation deficit occurs over the southeastern TP . The opposite scenario occurs during the negative phase of the NAO .

Union is strength: matrix elasticity and microenvironmental factors codetermine stem cell differentiation fate - Hongwei Lv; Lisha Li; Yin Zhang; Zhishen Chen; Meiyu Sun; Tiankai Xu; Licheng Tian; Man Lu; Min Ren; Yuanyuan Liu; Yulin Li (Cell and Tissue Research, 2015)

Overexpression of SIRT1 Induced by Resveratrol and Inhibitor of miR-204 Suppresses Activation and Proliferation of Microglia - Lihong Li; Qiang Sun; Yuqian Li; Yang Yang; Yanlong Yang; Tao Chang; Minghao Man; Longlong Zheng (Journal of Molecular Neuroscience, 2015)

Ferrovibrio xuzhouensis sp. nov., a cyhalothrin-degrading bacterium isolated from cyhalothrin contaminated wastewater - Man Song; Long Zhang; Bin Sun; Hao Zhang; Hui Ding; Qiang Li; Suhui Guo; Xing Huang (Antonie van Leeuwenhoek, 2015)

Development of a set of bacterial biosensors for simultaneously detecting arsenic and mercury in groundwater - Chi-Wei Huang; Shih-Hung Yang; Man-Wai Sun; Vivian Hsiu-Chuan Liao (Environmental Science and Pollution Research, 2015)

Tree-scale spatial variation of soil respiration and its influence factors in apple orchard in Loess Plateau - Rui Wang; Shengli Guo; Jishao Jiang; Defeng Wu; Nana Li; Yanjun Zhang; Qingfang Liu; Rujian Li; Zhiqi Wang; Qiqi Sun; Lanlan Du; Man Zhao (Nutrient Cycling in Agroecosystems, 2015)

Tobacco smoking, family history, and the risk of nasopharyngeal carcinoma: a case–referent study in Hong Kong Chinese - Shao-Hua Xie; Ignatius Tak-sun Yu; Lap Ah Tse; Joseph Siu Kie Au; June Sze Man Lau (Cancer Causes & Control, 2015)

Human health risk assessment of soil dioxin/furans contamination and dioxin-like activity determined by ethoxyresorufin-O-deethylase bioassay - Yu Bon Man; Ka Lai Chow; Hong Sheng Wang; Xiao Lin Sun; Sheng Chun Wu; Zong Wei Cai; Yuan Kang; Hui Li; Jin Shu Zheng; John P. Giesy; Ming Hung Wong (Environmental Science and Pollution Research, 2015)

Effects of La(III) and Ca(II) on Isolated Carassius auratus Liver Mitochondria: Heat Production and Mitochondrial Permeability Transition - Man Wu; Jia-Ling Gao; Mei-Xiang Sun; Ye-Zhong Zhang; Yi Liu; Jie Dai (Biological Trace Element Research, 2015)

Fragilariopsis kerguelensis response to iron enrichment regarding its growth, uptake of nutrients and trace metals, and changes in CO2, CH4, and N2O - Young Shin Kwon; Tae Siek Rhee; Sun Young Kim; Mi Seon Kim; Man Sik Choi; Eun Jin Yang; Young-Nam Kim (Ocean Science Journal, 2014)

Altererythrobacter oceanensis sp. nov., isolated from the Western Pacific - Yanliu Yang; Gaiyun Zhang; Zhilei Sun; Man Kit Cheung; Cheney Huang (Antonie van Leeuwenhoek, 2014)

Enhancement of Nasal HIV Vaccination with Adenoviral Vector-Based Nanocomplexes Using Mucoadhesive and DC-Targeting Adjuvants - Yuhong Jiang; Man Li; Zhirong Zhang; Tao Gong; Xun Sun (Pharmaceutical Research, 2014)

Hypoxia turns genotypic female medaka fish into phenotypic males - Catis Hin Ying Cheung; Jill Man Ying Chiu; Rudolf Shiu Sun Wu (Ecotoxicology, 2014)

Phanerochaete chrysosporium inoculation shapes the indigenous fungal communities during agricultural waste composting - Jiachao Zhang; Guangming Zeng; Yaoning Chen; Jie Liang; Chang Zhang; Binbin Huang; Weimin Sun; Ming Chen; Man Yu; Hongli Huang; Yi Zhu (Biodegradation, 2014)

Comparison of Digene Hybrid Capture 2, GeneMatrix PapilloScreen, and a PCR sequencing assay in detecting high-risk and probable high-risk oncogenic HPV genotypes in specimens from Korean women - Jae-Man Bae; Kyung Tae Min; Ji Young Shin; Soo-Kyung Shin; Soo Nyung Kim; Hyo-Pyo Lee; Soo-Ok Kim; Sun Pyo Hong (Archives of Virology, 2014)

The Novel Tetramethylpyrazine Bis-nitrone (TN-2) Protects Against MPTP/MPP+-Induced Neurotoxicity via Inhibition of Mitochondrial-Dependent Apoptosis - Daping Xu; Hongwei Duan; Zaijun Zhang; Wei Cui; Liang Wang; Yewei Sun; Ming Lang; Pui Man Hoi; Yifan Han; Yuqiang Wang; Simon MingYuen Lee (Journal of Neuroimmune Pharmacology, 2014)

Amino Acid, Fatty Acid, and Metal Compositions in Edible Parts of Three Cultured Economic Crabs: Scylla paramamosain, Portunus trituberculatus , and Eriocheir sinensis - Ke-Ji Jiang; Feng-Ying Zhang; Yan Pi; Li-Li Jiang; Zhong-Li Yu; Dan Zhang; Man-Man Sun; Lu-Jiao Gao; Zhen-Guo Qiao; Ling-Bo Ma (Journal of Aquatic Food Product Technology, 2014)

Attachment of Acidithiobacillus ferrooxidans onto different solid substrates and fitting through Langmuir and Freundlich equations - Le-Xian Xia; Zhen Shen; Tomas Vargas; Wen-Juan Sun; Ren-Man Ruan; Zhen-Da Xie; Guan-Zhou Qiu (Biotechnology Letters, 2013)

Local synchronization and amplitude of the fluctuation of spontaneous brain activity in attention-deficit/hyperactivity disorder: a resting-state fMRI study - Li An; Qing-Jiu Cao; Man-Qiu Sui; Li Sun; Qi-Hong Zou; Yu-Feng Zang; Yu-Feng Wang (Neuroscience Bulletin, 2013)

Cloning and characterization of a novel apolipoprotein gene, apolipoprotein AV, in tree shrews - Guoping Li; Huairong Luo; Guotao Sun; Guisheng Wu; Gang Wu; Yan Wang; Yong Man; Shu Wang; Jian Li; Baosheng Chen (Molecular Biology Reports, 2013)

RNAi suppression of β-N-acetylglucosaminidase (BmFDL) for complex-type N-linked glycan synthesis in cultured silkworm cells - Yudai Nagata; Jae Man Lee; Hiroaki Mon; Shigeo Imanishi; Sun Mee Hong; Shoji Komatsu; Yuji Oshima; Takahiro Kusakabe (Biotechnology Letters, 2013)

Major depressive disorder, panic disorder, and post-traumatic stress disorder in Korean subway drivers - Hyoung-Ryoul Kim; Hyeon Woo Yim; Sun-Jin Jo; Bongkyoo Choi; Seung Hee Jeong; Kang Sook Lee; Jong-Ik Park; Sung Man Chang (International Archives of Occupational and Environmental Health, 2013)

Combined Effects of PFOS and PFOA on Zebrafish (Danio rerio) Embryos - Guanghui Ding; Jing Zhang; Yihong Chen; Luyan Wang; Man Wang; Deqi Xiong; Yeqing Sun (Archives of Environmental Contamination and Toxicology, 2013)

Hoeflea halophila sp. nov., a novel bacterium isolated from marine sediment of the East Sea, Korea - Man-Young Jung; Kee-Sun Shin; Suyeon Kim; So-Jeong Kim; Soo-Je Park; Jong-Geol Kim; In-Tae Cha; Mi-Na Kim; Sung-Keun Rhee (Antonie van Leeuwenhoek, 2013)

Fosinopril Attenuates the Doxorubicin-induced Cardiomyopathy by Restoring the Function of Sarcoplasmic Reticulum - Ya-chen Zhang; Yong Tang; Min Zhang; Jian Chen; Qing Zhou; Ying-gang Sun; Man-tian Chen; Wei-ping Xu (Cell Biochemistry and Biophysics, 2012)

A profile of expressed sequence tags in newly developing leaves of Aralia elata seem - Kyung Hwan Boo; Doseung Lee; Seong Beom Jin; Seong Cheol Kim; Jae Hoon Kim; Jin-Man Lee; Somi Kim Cho; Dong Sun Lee; Key Zung Riu (Horticulture, Environment, and Biotechnology, 2012)

Clinical Implications of Quantitative Electroencephalography and Current Source Density in Patients with Alzheimer’s Disease - Ji-Sun Kim; Seung-Hwan Lee; Gewnhi Park; Sangrae Kim; Sung-Man Bae; Do-Won Kim; Chang-Hwan Im (Brain Topography, 2012)

Fluid Flow-Induced Calcium Response in Early or Late Differentiated Osteoclasts - Ping Li; Man Hu; Shujin Sun; Yan Zhang; Yuxin Gao; Mian Long; Bo Huo; Ding Zhang (Annals of Biomedical Engineering, 2012)

Isolation of a novel gene encoding a 3,5,6-trichloro-2-pyridinol degrading enzyme from a cow rumen metagenomic library - Renukaradhya K. Math; Shah Md. Asraful Islam; Kye Man Cho; Sun Joo Hong; Jong Min Kim; Myoung Geun Yun; Ji Joong Cho; Jae Young Heo; Young Han Lee; Hoon Kim; Han Dae Yun (Biodegradation, 2010)

Enhancement of tolerance to soft rot disease in the transgenic Chinese cabbage (Brassica rapa L. ssp. pekinensis) inbred line, Kenshin - Enkhchimeg Vanjildorj; Seo Young Song; Zhi Hong Yang; Jae Eul Choi; Yoo Sun Noh; Suhyoung Park; Woo Jin Lim; Kye Man Cho; Han Dae Yun; Yong Pyo Lim (Plant Cell Reports, 2009)

Comparative Analysis of the glg Operons of Pectobacterium chrysanthemi PY35 and Other Prokaryotes - Kye Man Cho; Woo Jin Lim; Renukaradhya K. Math; Shah Md. Asraful Islam; Sun Joo Hong; Hoon Kim; Han Dae Yun (Journal of Molecular Evolution, 2008)

Changes in the activity of the multifunctional β-glycosyl hydrolase (Cel44C-Man26A) from Paenibacillus polymyxa by removal of the C-terminal region to minimum size - Kye-Man Cho; Renukaradhya K. Math; Su-Young Hong; Shah Md. Asraful Islam; Jong-Ok Kim; Sun-Joo Hong; Hoon Kim; Han-Dae Yun (Biotechnology Letters, 2008)

Construction of the bifunctional enzyme cellulase-β-glucosidase from the hyperthermophilic bacterium Thermotoga maritima - Su-Young Hong; Jin-Suk Lee; Kye-Man Cho; Renukaradhya K. Math; Yong-Hee Kim; Sun-Joo Hong; Yong-Un Cho; Soo-Jeong Cho; Hoon Kim; Han-Dae Yun (Biotechnology Letters, 2007)

Assembling a novel bifunctional cellulase–xylanase from Thermotoga maritima by end-to-end fusion - Su Young Hong; Jin Suk Lee; Kye Man Cho; Renukaradhya K Math; Yong Hee Kim; Sun Joo Hong; Yong Un Cho; Hoon Kim; Han Dae Yun (Biotechnology Letters, 2006)

Size selectivity of diamond and square mesh codends for hairfin anchovy Setipinna taty in Chinese stow net fisheries - Man Chang SUN; Jian ZHANG; Liu Xiong XU (Fisheries Science, 2006)

Study on spatial autocorrelation of urban land price distribution in Changzhou city of Jiangsu Province - Zhong-gang Liu; Man-chun Li; Yan Sun; Wen-bo Ma (Chinese Geographical Science, 2006)

Influence of temperature fluctuation on thermophilic anaerobic digestion of municipal organic solid waste - Man-chang Wu; Ke-wei Sun; Yong Zhang (Journal of Zhejiang University-SCIENCE B, 2006)

Characteristics of thermal and geopotential height differences between continent and ocean and its role in the strength of the Asian summer monsoon - Andrea Silver-man; Jilin Sun (Journal of Ocean University of China, 2005)

Identification ofporphyra lines (rhodophyta) by AFLP DNA fingerprinting and molecular markers - Jian Wei Sun; Min De Jin; Chun Jiang Zhou; Qing Kai Yang; Man Li Weng; Lin De Duan; Pu Xu; Jia Hai Ma; Bin Wang (Plant Molecular Biology Reporter, 2005)

Purification and characterization of recombinant human liver prolidase expressed in Saccharomyces cerevisiae - Shu-Hao Wang; Qing-Wen Zhi; Man-Ji Sun (Archives of Toxicology, 2005)

Extraction of Speaker Features from Different Stages of DSR Front-Ends for Distributed Speaker Verification - Man-Wai Mak; Chin-Hung Sit; Sun-Yuan Kung (Genetic Resources and Crop Evolution, 2005)

Production, purification, and characterization of a novel thermostable serine protease from soil isolate, Streptomyces tendae - Chi-Nam Seong; Jung-Sun Jo; Sang-Ki Choi; Si-Wouk Kim; Sung-Jun Kim; Oh-Hyung Lee; Ji-Man Han; Jin-Cheol Yoo (Biotechnology Letters, 2004)

The 5′-end of the porcine perinatal myosin heavy chain gene shows alternative splicing and is clustered with repeat elements - Nuno Da Costa; Nicolas Beuzen; Irene Johnston; Christine McGillivray; Yuh-man Sun; Kin Chow Chang (Journal of Muscle Research and Cell Motility, 2000)

A new human prostate carcinoma cell line, 22Rv1 - R. Michael Sramkoski; Thomas G. Pretlow; Joseph M. Giaconia; Theresa P. Pretlow; Stuart Schwartz; Man-Sun Sy; Susan R. Marengo; Johng S. Rhim; Desheng Zhang; James W. Jacobberger (In Vitro Cellular & Developmental Biology - Animal, 1999)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

Over-expression of human CD44s in murine 3T3 cells: selection against during primary tumorigenesis and selection for during micrometastasis - Priit Kogerman; Man-Sun Sy; Lloyd A. Culp (Clinical & Experimental Metastasis, 1998)